Sublithospheric and lithospheric diamonds from the Candle Lake C29/30 kimberlite, Sask Craton - Andrea Pezzera; Fabrizio Nestola; Richard A. Stern; Aleksey Agashev; Perry Ksyniuk; Thomas Stachel; D. Graham Pearson (Lithos, 2026)

Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Remote Sensing for Irrigation Water Management—The State of the Art and Prospects for Near‐Future Operations - Wim G. M. Bastiaanssen; Chris Perry; Royce Dalby; Yasir Mohamed; Xueliang Cai; Poolad Karimi; IJsbrand de Jong; Pasquale Steduto; Marat Beksultanov; Christopher C. M. Neale; David Molden; Waqas Awan; et al. (Irrigation and Drainage, 2026)
A recent UN report describes many regions as facing ‘water bankruptcy, ’ a condition in which available water resources can no longer meet existing demands. In practice, this means irrigation will likely bear the greatest burden of future water‐use reductions, a complicated and fraught decision to make given its critical role in food security. This review paper highlights the growing range of information now available through remote sensing technologies to support planners, irrigation managers and farmers. These data include cropping patterns, crop yields, water consumption, farmgate water and tubewell water deliveries, soil moisture and root‐zone water storage, among others. The paper also reviews current applications of remote sensing, which remain too often constrained to the scientific community, and recommends the development and dissemination of standardized irrigation analytics and diagnostic tools. Government irrigation and water agencies are encouraged to integrate these emerging spatial data sources into both strategic planning and real‐time management from field to scheme scale and provide a stronger foundation of key performance indicator (KPI). Bridging this information gap will require startups and technology providers to translate advanced data products into practical, user‐friendly tools tailored to the needs of the irrigation sector.

Prioritising actions over space and time in multi-habitat ecological restoration: Insights from indicator species in coastal seascapes - Ben L. Gilby; Andrew D. Olds; Michael Sievers; Maria L. Vozzo; Brittany B. Elliott; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Ashley J. Rummell; Christopher J. Henderson (Landscape and Urban Planning, 2026)

The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

The impact of serial translocation bottlenecks on the genetic diversity of Anegada Rock Iguanas (Cyclura pinguis) in the British Virgin Islands - Giuliano Colosimo; Zachary Dykema; Mark E. Welch; Gad Perry; Zachary Harlow; Heidi Davis; Kelly A. Bradley; Gabriele Gentile; Glenn P. Gerber (Conservation Genetics, 2026)

Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

Australian native foods in gastronomy: Culture, ethics, culinary practice, and supply chains - Keely Rose Perry; Melissa A. Fitzgerald; Bronwyn Fredericks; Dale Chapman; Joseph Robert Nastasi (Food and Humanity, 2026)

Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

An Urban Taonga: The Distribution and Abundance of Tuna in Urban Streams Across Tāmaki Makaurau, Aotearoa‐New Zealand - Nicole A. Whitelock; Kevin S. Simon; George L. W. Perry (New Zealand Journal of Marine and Freshwater Research, 2026)
Freshwater eels of the Anguilla genus are experiencing global decline, largely driven by human activity. In Aotearoa‐New Zealand, tuna (both shortfin and longfin eels) are similarly affected, with habitat fragmentation and modification key drivers of their decline. We investigated the distribution and abundance of tuna across regional, catchment and reach‐level scales in an urban environment. We developed species distribution models (SDMs) across the Tāmaki Makaurau (Auckland) region to explore patterns in tuna distribution across an urbanisation gradient. Additionally, we conducted a field survey across an urban catchment in Tāmaki Makaurau to assess the local habitat features associated with tuna presence and abundance. The predictive power of our SDMs was limited, and the field survey revealed that tuna were broadly distributed throughout the urban catchment, displaying only weak associations with specific habitat features. These findings suggest that in the absence of movement barriers, tuna can occupy a wide range of habitats throughout urban streams. However, the presence of tuna may not indicate suitable habitat for survival and growth, as their robust and opportunistic nature allows them to persist even in suboptimal environments.

Who needs closure? Estimating abundance with a Markovian availability model for geographically open removal sampling - Russell W. Perry; Adam C. Pope; A. Noble Hendrix; Joseph E. Kirsch; Bryan G. Matthias; Michael J. Dodrill (Ecology, 2026)
Removal sampling is an important method for estimating abundance, but nearly all removal models assume closure during sampling. Yet, closure may be difficult to assume, evaluate, or enforce in many settings. To address situations where populations are geographically open between each removal sample, we incorporated a Markovian availability process into an N‐mixture model framework. This model relates local abundance available for sampling to a superpopulation through recruitment of new individuals to the sampling area. To test the model, we (1) conducted parameter identifiability analysis, (2) fit the model to removal data generated from a random walk movement model, and (3) analyzed a case study of empirical removal data. Parameters were increasingly identifiable as capture probability exceeded 0.25 and removal samples increased from 3 to 6. Abundance estimates were unbiased when parameters were identifiable, except for scenarios that simulated a behavioral response to sampling. For our case study, the model estimated negligible recruitment for benthic‐oriented fishes, indicating closure, but we found evidence against closure for juvenile Chinook salmon, a highly mobile species. Our removal model allows researchers to formally test closure assumptions, to estimate the degree of closure, and to estimate abundance without bias when closure is violated.

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

A habitability lens to boost effective local climate adaptation - A.K. Magnan; V.K.E. Duvat; J. Bell; S.D. Donner; J.D. Ford; P.D. Nunn; C. Perry; T. Spencer; C.C.C. Wabnitz; I. White; J. Butler; A. McCarthy; et al. (Environmental Science & Policy, 2026)

Dynamic thumb localization and its adaptation: quantification with a novel robotic task - Luis Garcia-Fernandez; Andria J. Farrens; Christopher A. Johnson; Vicky Chan; Joel C. Perry; Eric T. Wolbrecht; David J. Reinkensmeyer (Experimental Brain Research, 2026)
The thumb plays a crucial role in hand function, yet its proprioceptive abilities remain poorly understood. Here we quantified dynamic thumb localization ability, as well as how this ability adapts to a perturbation, in unimpaired participants. For this, we developed a novel task in which a robot moved the thumb in a circle and participants pressed a button when they felt their thumb aligning with a target point on a screen, receiving visual error feedback in the form of a ball jumping toward the target after they pushed the button. The task also incorporated a propriovisual rotational perturbation to elicit and measure adaptation. To characterize thumb localization ability, we varied thumb speed and rotation diameter, assessed the effect of the propriovisual rotational perturbation, and compared index finger performance. Following task familiarization, average thumb localization error was relatively consistent, with a constant error (CE) of − 5.9°, variable error (VE) of 25.2°, and absolute error (AE) of 29.2°. Errors did not change significantly with speed or circle diameter. Reversing thumb rotation temporarily increased error followed by rapid error adaptation across the next 20 trials, as would be expected if individuals adapted using a body-centered (movement-aligned) frame of reference rather than a world-centered spatial frame. Localization error was comparable for the thumb and the index finger error for the same task and was correlated with a different, robotic assessment of finger proprioception (ρ = 0.61, p = 0.001). These findings indicate that dynamic thumb localization is somewhat inaccurate, although it can leverage visual feedback within a body-centered reference frame to adapt. Further, in unimpaired adults, the dynamic localization abilities of the thumb and index finger are related.

Towards a global barcode reference library for subterranean fauna - Michelle T. Guzik; Jake Thornhill; Mieke van der Heyde; Danielle N. Stringer; Nicole E. White; Mattia Saccò; Perry G. Beasley-Hall; Paul Nevill; Rachael A. King; Steven J.B. Cooper; Andrew D. Austin (Science of The Total Environment, 2026)

Multi-year water level drawdown and wildlife grazing drive wetland vegetation succession - Kerstin Bouma; Gabriela Carrasco Oliva; Mats I. Douma; Perry Cornelissen; Mennobart R. van Eerden; Ralph J.M. Temmink; Bart A. Nolet; Elisabeth S. Bakker (Ecological Engineering, 2026)

Restoring the wild east: Predicting public support for cougar and red wolf reintroduction in the eastern United States - Benjamin Ghasemi; Jeremy T. Bruskotter; John A. Vucetich; L. Mark Elbroch; Robyn S. Wilson; Neil H. Carter; Axel Moehrenschlager; Shelby Perry; Joseph W. Hinton (Biological Conservation, 2026)

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Use of mercury in mining 125 years ago continues to impact waterfowl populations: Implications for current artisanal gold mining - Morgan A. Byrne; Mae Sexauer Gustin; Chris A. Nicolai; Perry J. Williams (Science of The Total Environment, 2025)

Reproductive risk of Neonicotinoids: A review of male rodent studies - Sumaiya S. Irfan; Veronica G. Sanchez; Michael S. Bloom; Helen B. Chin; Virginia Espina; Jenna R. Krall; Anna Z. Pollack; Lance A. Liotta; Melissa J. Perry (Environmental Research, 2025)

An integrative taxonomy investigation unravels a cryptic species of Mobula Rafinesque, 1810 (Mobulidae, Myliobatiformes), from the Atlantic Ocean - Nayara Bucair; Silvia Hinojosa-Alvarez; Andrea Denise Marshall; Jessica Pate; Carlo Leopoldo Bezerra Francini; Amana Guedes Garrido; Katia Cristina Cruz Capel; Thiago Silva Loboda; Jhonatas Sirino Monteiro; Carlos Eduardo Malavasi Bruno; Claudia Francesca Vaga; Alistair D. M. Dove; et al. (Environmental Biology of Fishes, 2025)

Community Asset Mapping Builds a Foundation for a K-2 Nutrition-based STEM Program in Mississippi Public Libraries - A. Perry; I. Thornton; S. Mason; P. Maamah; A. Bansah; A. Rutherford; A. Caldwell; D. Holben (Journal of the Academy of Nutrition and Dietetics, 2025)

Community Assets and Needs: A Survey of Mississippi Public Libraries for development of a K-2 Nutrition-based STEM Program - A. Perry; I. Thornton; S. Mason; A. Bansah; P. Maamah; A. Rutherford; A. Caldwell; D. Holben (Journal of the Academy of Nutrition and Dietetics, 2025)

Museum Genomics Reveals Temporal Genetic Stasis and Global Genetic Diversity in Arabidopsis thaliana - Lua Lopez; Patricia L. M. Lang; Stephanie Marciniak; Logan Kistler; Sergio M. Latorre; Asnake Haile; Eleanna Vasquez Cerda; Diana Gamba; Yuxing Xu; Patrick Woods; Mistire Yifru; Jeffrey Kerby; et al. (Molecular Ecology, 2025)
Global patterns of population genetic variation through time offer a window into evolutionary processes that maintain diversity. Over time, lineages may expand or contract their distribution, causing turnover in population genetic composition. At individual loci, migration, drift and selection (among other processes) may affect allele frequencies. Museum specimens of widely distributed species offer a unique window into the genetics of understudied populations and changes over time. Here, we sequenced genomes of 130 herbarium specimens and 91 new field collections of Arabidopsis thaliana and combined these with published genomes. We sought a broader view of genomic diversity across the species and to test if population genomic composition is changing through time. We documented extensive and previously uncharacterised diversity in a range of populations in Africa, populations that are under threat from anthropogenic climate change. Through time, we did not find dramatic changes in genomic composition of populations. Instead, we found a pattern of genetic change every 100 years of the same magnitude seen when comparing Eurasian populations that are 185 km apart, potentially due to a combination of drift and changing selection. We found only mixed signals of polygenic adaptation at phenology and physiology QTL. We did find that genes conserved across eudicots show altered levels of directional allele frequency change, potentially due to variable purifying and background selection. Our study highlights how museum specimens can reveal new dimensions of population diversity and show how wild populations are evolving in recent history.

Characterising the innate immune response in breech strike resistant and non-selected sheep to the sheep blowfly (Lucilia cuprina) - Sugandhika G. Welikadage; Habtamu B. Derseh; Trent Perry; Clare A. Anstead; Jean-Pierre Y. Scheerlinck; Vern M. Bowles (Veterinary Immunology and Immunopathology, 2025)

Novel resistance to tobacco etch virus in peppers (Capsicum spp.) - Kevin M. Crosby; Sixto A. Marquez; Olufemi Alabi; Kevin Ong; Stephen Perry (Euphytica, 2025)
Tobacco etch virus (TEV) is a pathogen that affects peppers all over the world. It causes serious losses, and it is difficult to control since it has many aphid vectors. Because these aphids move around, and transmit TEV in a non-persistent manner, many applications of pesticides would be necessary to reduce TEV incidence, leading to more environmental pollution and destruction of beneficial predator insects. Therefore, host plant resistance is the best solution for TEV. Peppers ( Capsicum spp.) exhibit ample genetic variability. Numerous resistance genes against TEV have been documented over the past 70 years. However, these are all recessive in nature. This has made deployment in hybrids more difficult and therefore, not many TEV resistant pepper cultivars have been released. The pepper breeding project at Texas A&M AgriLife Research screened over 200 USDA plant introductions from 6 species for resistance to TEV with both natural field infection and controlled inoculations at Weslaco. ELISA tests and visual assessments of symptoms of the virus in the plants were performed. Four accessions not previously characterized as resistant were identified with mild or no symptoms. These included two C. chinense and two C. baccatum accessions. An interspecific population of C. annuum ‘serrano’ x C. baccatum var. baccatum was developed to study the resistance from that wild type. Chi-square analysis indicated that resistance is controlled by a single, dominant gene, which will facilitate the development of resistant varieties using traditional breeding procedures such as backcrossing.

Neighborhood environmental vulnerability factors strongly drove COVID-19 fatality and excess all-cause mortality in New York City, while long-term air pollutant associations were weak and varied - Alexander Azan; Sneha Kannoth; Cong Zhang; Mehr Shafiq; Earle C. Chambers; Perry E. Sheffield; Sandra S. Albrecht; Azure Thompson; Jennifer Woo Baidal; Min Qian; Stephanie Lovinsky-Desir; Jeanette A. Stingone (Science of The Total Environment, 2025)

A novel approach for quantifying elongated airborne mineral particles (EMPs) using an automated scanning electron microscope (SEM) - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Ayrton Hamilton; Wenxia (Wendy) Fan; Shuoyu Chen; Nick Talbot; Shanon Lim; Jed Januch; Martin Brook; Brett Wells; David E. Williams; et al. (Atmospheric Environment, 2025)

Net primary production in the Labrador Sea between 2014 and 2022 derived from ocean colour remote sensing based on ecological regimes - E. Devred; S. Clay; M. Ringuette; T. Perry; M. Amirian; A. Irwin; Z. Finkel (Remote Sensing of Environment, 2025)

Play and peril: Displacement drivers and types across recreation motivations in crowding and wildfire-prone southern California national forests - Alyssa S. Thomas; Erin E. Budzyn; Elizabeth E. Perry; Brian A. Peterson; José J. Sánchez (Journal of Outdoor Recreation and Tourism, 2025)

Estimating coral reef carbonate budgets using Structure-from-Motion photogrammetry - Hannah C. Barkley; Ariel A. Halperin; Damaris Torres-Pulliza; Mia S. Lamirand; Courtney S. Couch; Candace E. Alagata; Rebecca M. Weible; Joy N. Smith; Thomas A. Oliver; Chris T. Perry (Coral Reefs, 2025)

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Disentangling a genome-wide mosaic of conflicting phylogenetic signals in Western Rattlesnakes - Justin M. Bernstein; Yannick Z. Francioli; Drew R. Schield; Richard H. Adams; Blair W. Perry; Keaka Farleigh; Cara F. Smith; Jesse M. Meik; Stephen P. Mackessy; Todd A. Castoe (Molecular Phylogenetics and Evolution, 2025)

ICESat-2 bathymetry algorithms: A review of the current state-of-the-art and future outlook - Jaehoon Jung; Christopher E. Parrish; Lori A. Magruder; Joan Herrmann; Suhong Yoo; Jeffrey S. Perry (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Survival, Travel Time, and Use of Migration Routes by Juvenile Steelhead in a Modified River Estuary - Adam C. Pope; Russell W. Perry; Dalton J. Hance; Rebecca A. Buchanan (Estuaries and Coasts, 2025)

Advances in our understanding of the estrous cycle and applications for improving targeted reproductive management in livestock - Robert A. Cushman; Shelby L. Rosasco; Kacie L. McCarthy; Alexandria P. Snider; George A. Perry; Clay A. Lents (Domestic Animal Endocrinology, 2025)

Investigating eye lens composition for stable isotope analysis in fishes: a comparison between Chondrichthyes and Actinopterygii - Jonathon P. Kuntz; Miranda Bell-Tilcock; Julie L. Vecchio; Amy A. Wallace; Anna M. Sturrock; Sean M. Perry; Sora L. Kim (Environmental Biology of Fishes, 2025)
Life history ecology provides a framework for understanding the complex interactions between organisms and their environments but is challenging to resolve for long-lived and migratory species. In fishes, the combination of movement and foraging ecology is predominantly explored with stable isotope analysis (SIA) of accretionary tissues, such as otoliths. An alternative archival tissue validated for SIA in Actinopterygii (i.e., ray-finned fishes) is the proteinaceous eye lens and its growth layers (laminae). Here, we aim to expand the SIA of laminae to include Chondrichthyes (cartilaginous fishes; sharks, skates, rays, sawfish, and chimeras). We observe that urea in the eye lens drives patterns of elemental composition (i.e., C:N ratio) for Chondrichthyes, but the isotopic effect of urea is negligible. Actinopterygian fishes exhibit consistent C:N ratios across eye lenses, while chondrichthyan eye lens laminae C:N ratios decrease from the inner post-apoptotic laminae to outer pre-apoptotic laminae. After confirming the presence of urea in the Leopard Shark ( Triakis semifasciata ) eye lens laminae with attenuated total reflectance (ATR)-Fourier transform infrared (FTIR) spectroscopy and urea assays, we successfully removed urea from eye lens laminae via three deionized water rinses. Subsequently, the C:N ratios of post-urea extracted Leopard Shark eye lens laminae exhibited similar patterns to actinopterygian fishes. Urea removal from Leopard Shark eye lens laminae increased in δ 15 N values as expected, but the isotopic effect was within analytical error. Our results indicate the utility of chondrichthyan eye lens laminae as chronological tissues for SIA. However, there are isotopic effects dependent on urea concentrations. This study demonstrates the need for inter-taxa comparison when establishing novel methodologies in SIA.

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Was extinction of New Zealand's avian megafauna an unavoidable consequence of human arrival? - Sean Tomlinson; Mark V. Lomolino; Jamie R. Wood; Atholl Anderson; George L.W. Perry; Janet M. Wilmshurst; Jeremy J. Austin; Damien A. Fordham (Science of The Total Environment, 2025)

Metagenomics unveils the role of hospitals and wastewater treatment plants on the environmental burden of antibiotic resistance genes and opportunistic pathogens - Reshma Silvester; William B. Perry; Gordon Webster; Laura Rushton; Amy Baldwin; Daniel A. Pass; Nathaniel Healey; Kata Farkas; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; et al. (Science of The Total Environment, 2025)

No General Trend in Functional Diversity in Bird and Mammal Communities Despite Compositional Change - Kari E. A. Norman; Perry de Valpine; Carl Boettiger (Global Ecology and Biogeography, 2025)
Aim Despite unprecedented environmental change due to anthropogenic pressure, recent work has found increasing dissimilarity due to turnover but no overall trend in species diversity through time at the local scale. Functional diversity provides a potentially powerful alternative approach for understanding community composition by linking shifts in species identity to the characteristics that underpin ecosystem processes. Here we present the first multitaxa, multisystem analysis of functional diversity and composition through time. Location Global, with a North American focus. Time Period 1923–2014. Major Taxa Studied Mammals, Birds. Methods We paired thousands of bird and mammal assemblage time series from the BioTIME database with existing trait data representative of species' functional roles to reconstruct time series of functional diversity and composition metrics. Our dataset included 2432 time series of yearly observations from 50 studies with a maximum spatial extent of 95 km 2 . Using generalised linear mixed models, we estimated general and study‐level trends for those metrics. Results We found no overall temporal trends in functional diversity metrics. Study characteristics such as taxa, realm, biome, or protection status did not distinguish between types of change exhibited by communities. We found evidence of a temporal increase in fish consumption across all communities but no evidence to support multiple predictions for specific traits, including decreasing body size, dietary shifts or changes in bird foraging strata. Main Conclusions General temporal trends indicate that on the aggregate, studies do not exhibit consistent changes in functional diversity across many taxa, biomes and realms. At the study level, the majority of studies showed no temporal trends in species or functional diversity, with the remainder of the studies falling into broad categories of functional diversity change independent of species richness, functional redundancy loss (species richness declines with functional richness maintained) and increasing species richness sometimes accompanied by increasing functional richness.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Analysis of nonsynonymous SNPs in candidate genes that influence bovine temperament and evaluation of their effect in Brahman cattle - Gilberto Ruiz-De-La-Cruz; Ana María Sifuentes-Rincón; Francisco Alejandro Paredes-Sánchez; Gaspar Manuel Parra-Bracamonte; Eduardo Casas; David G. Riley; George A. Perry; Thomas H. Welsh; Ronald D. Randel (Molecular Biology Reports, 2024)
Background Temperament is an important production trait in cattle and multiple strategies had been developed to generate molecular markers to assist animal selection. As nonsynonymous single nucleotide polymorphisms are markers with the potential to affect gene functions, they could be useful to predict phenotypic effects. Genetic selection of less stress-responsive, temperamental animals is desirable from an economic and welfare point of view. Methods and results Two nonsynonymous single nucleotide polymorphisms identified in HTR1B and SLC18A2 candidate genes for temperament were analyzed in silico to determine their effects on protein structure. Those nsSNPs allowing changes in proteins were selected for a temperament association analysis in a Brahman population. Transversion effects on protein structure were evaluated in silico for each amino acid change model, revealing structural changes in the proteins of the HTR1B and SLC18A2 genes. The selected nsSNPs were genotyped in a Brahman population ( n = 138), and their genotypic effects on three temperament traits were analyzed: exit velocity, pen score, and temperament score. Only the SNP rs209984404-HTR1B (C/A) showed a significant association ( P = 0.0144) with pen score. The heterozygous genotype showed a pen score value 1.17 points lower than that of the homozygous CC genotype. Conclusion The results showed that in silico analysis could direct the selection of nsSNPs with the potential to change the protein. Non-synonymous single nucleotide polymorphisms causing structural changes and reduced protein stability were identified. Only rs209984404-HTR1B shows that the allele affecting protein stability was associated with the genotype linked to docility in cattle.

Stress-Induced Constraint on Expression Noise of Essential Genes in E. coli - Perry A. LaBoone; Raquel Assis (Journal of Molecular Evolution, 2024)

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

The suppression of lower leg electromyography when walking in textured foot orthoses - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

Producing 3D radargrams from orbital radar sounding data at Mars: History, results, methods, lessons and plans - Frederick J. Foss; Nathaniel E. Putzig; Bruce A. Campbell; Stewart A. Levin; Matthew R. Perry; John W. Holt; Michael S. Christoffersen; Isaac B. Smith; Gareth A. Morgan; Aaron T. Russell (Icarus, 2024)

A new numerical model of the HF antenna of the Mars Reconnaissance Orbiter’s (MRO) Shallow Radar (SHARAD) and first results from a test at a high-angle spacecraft roll - Alessandro DiCarlofelice; Piero Tognolatti; Fabrizio Bernardini; Renato Croci; Gareth A. Morgan; Matthew R. Perry; Nathaniel E. Putzig (Icarus, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Science results from sixteen years of MRO SHARAD operations - Nathaniel E. Putzig; Roberto Seu; Gareth A. Morgan; Isaac B. Smith; Bruce A. Campbell; Matthew R. Perry; Marco Mastrogiuseppe (Icarus, 2024)

Dynamic development of the Athabasca Valles outflow system from volcanic facies and 15 m scale roughness - Russell C. Miller; Cyril Grima; Sean P.S. Gulick; Timothy A. Goudge; Aaron T. Russell; Matthew R. Perry; Nathaniel E. Putzig; Bruce A. Campbell (Icarus, 2024)

Quantifying Environmental and Spatial Patterns of Fish on Log Snags to Optimise Resnagging in Coastal Seascapes - Lucy A. Goodridge Gaines; Jesse D. Mosman; Christopher J. Henderson; Andrew D. Olds; Hannah J. Perry; Ben L. Gilby (Estuaries and Coasts, 2024)
Long-term declines in coastal water quality and sedimentation can affect the restoration success of ecosystems such as seagrass and shellfish reefs. Resnagging coastal seascapes offers a potential alternative restoration method that is not reliant on abiotic conditions and which may enhance degraded landscapes for fish and fisheries. While common in freshwater ecosystems, such interventions are unusual for coastal seascapes despite log snags supporting significant benefits for coastal fish. In this study, we identify the spatial (e.g. seascape connectivity), habitat condition (e.g. log snag complexity and food availability) and water quality variables that best explain variation in fish assemblages on log snags to help prioritise the placement and design of resnagging efforts in estuaries. We surveyed fish assemblages on log snags using underwater videography at 363 sites across 13 estuaries in southeast Queensland, Australia, over 3 years. Sites less than 10,000 m from the estuary mouth, more than 2500 m from urban structures and located in water depths of < 3 m harboured more diverse fish assemblages. Sites less than 10,000 m from the estuary mouth with lower (< 25%) algae cover harboured greater total fish abundance and harvested fish abundance. Similar trends were found for the abundance of individuals from key functional groups, although these trends were mediated by other seascape contexts (e.g. the area of natural habitat) and water quality variables (e.g. chlorophyll-a concentration and dissolved oxygen saturation). Our results indicate that log snag placement in estuaries for benefits to fish and fisheries can be maximised if sites are planned strategically.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Within-field extrapolation away from a soil moisture probe using freely available satellite imagery and weather data - R. G. V. Bramley; E. M. Perry; J. Richetti; A. F. Colaço; D. J. Mowat; C. E. M. Ratcliff; R. A. Lawes (Precision Agriculture, 2024)
Recognition of the importance of soil moisture information to the optimisation of water-limited dryland cereal production has led to Australian growers being encouraged to make use of soil moisture sensors. However, irrespective of the merits of different sensing technologies, only a small soil volume is sensed, raising questions as to the utility of such sensors in broadacre cropping, especially given spatial variability in soil water holding capacity. Here, using data collected from contrasting sites in South Australia and Western Australia over two seasons, during which either wheat or barley were grown, we describe a method for extrapolating soil moisture information away from the location of a probe using freely-available NDVI time series and weather data as covariates. Relationships between soil moisture probe data, cumulative NDVI (ΣNDVI), cumulative net precipitation (ΣNP) and seasonal growing degree days (GDD) were significant ( P < 0.0001). In turn, these could be used to predict soil moisture status for any location within a field on any date following crop emergence. However, differences in ΣNDVI between different within-field zones did not fully explain differences in the soil moisture from multiple sensors located in these zones, resulting in different calibrations being required for each sensor or zone and a relatively low accuracy of prediction of measured soil moisture (R 2 adj ~ 0.4–0.7) which may not be sufficient to support targeted agronomic decision-making. The results also suggest that at any location within a field, the range of variation in soil moisture status down the soil profile on any given date will present as greater than the spatial variation in soil moisture across the field on that date. Accordingly, we conclude that, in dryland cereal cropping, the major value in soil moisture sensors arises from an enhanced ability to compare seasons and to relate similarities and differences between seasons as a guide to decision-making.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Flood effects on estuarine fish are mediated by seascape composition and context - Christopher J. Henderson; Andrew D. Olds; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Hayden P. Borland; Ben L. Gilby (Marine Biology, 2024)
Estuaries are crucial feeding, nursery and resting sites for fish but can also be subject to the impacts of severe flooding. The environmental features of estuaries can mediate how they respond to these impacts. For example, the size, configuration, and context of estuarine habitats across seascapes affects the value of patches for fish, and so fish assemblages at sites with a greater habitat extent or closer to the mouth of an estuary may rebound more quickly from flooding. We investigated how a once in 100-year flood event affected fish assemblages at approximately 600 sites across 13 estuaries and six estuarine habitats (bare sediments, log snags, mangrove forests, rocky structures, saltmarsh and seagrass meadows) in southeast Queensland, Australia, and determined whether flood impacts were mediated by the position of sites within the broader estuarine seascape. Sites were surveyed annually in 2020/2021 (pre-flood) and 2022 (6 months post-flood) using underwater videography. Flooding modified the structure of the fish community and reduced the abundance of fish targeted by local fisheries in all six habitats. Crucially, flood effects on fish were greater at sites near more expansive urbanisation in some ecosystems, but lower at sites nearer to the estuary mouth. Maximising the extent of natural habitats across estuaries can mediate the effects of floods and should be priorities for restoration and management plans seeking to maintain biodiversity and fisheries productivity in the face of increasing climate-related disturbances.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Kelp holdfast microclimates buffer invertebrate inhabitants from extreme temperatures - Frances Perry; Grant A. Duffy; Miles D. Lamare; Ceridwen I. Fraser (Marine Environmental Research, 2024)

Resilient forests for the future - Annika Perry; Filippos A. Aravanopoulos; Katharina Birgit Budde; Ole Kim Hansen; Christian Rellstab; Hilke Schroeder; Alexandru Lucian Curtu (Tree Genetics & Genomes, 2024)
Forest ecosystems are of global importance, ecologically, economically and culturally. However, despite their fundamental role in mitigating the worst effects of climate change, to date there have been surprisingly few resources devoted to defining, conserving and planning resilient forests for the future. Progress in this field of research, which requires international and interdisciplinary cooperation, collaboration and communication, was presented and discussed at the second biannual conference of the European Research Group, Evoltree ( https://www.evoltree.eu ). Over four days more than 140 scientists met to share developments and to discuss forest ecology, genetics, genomics and evolution with a focus on realising “Resilient Forests for the Future”. From examining evolutionary dynamics and using the past to understand future responses, to evaluating breeding approaches and the sustainable use of forest genetic resources, the conference addressed critical themes with relevance to this topic. The role of genomics in conservation, investigation of biotic interactions and identifying climate resilient forests were also explored. Finally, innovative methods and approaches which promise to increase the scale and speed with which forest evolutionary research can progress were introduced and evaluated. The Evoltree network and conference series provides invaluable opportunities to share knowledge and increase collaboration on forest genetic research, the need for which has never been greater or more urgent.

A Community-Based Health Risk Assessment Following the Gold King Mine Spill: Results from the Gold King Mine Spill Diné Exposure Project - Yoshira Ornelas Van Horne; Karletta Chief; Perry H. Charley; Mae-Gilene Begay; Nathan Lothrop; Robert A. Canales; Paloma I. Beamer (Exposure and Health, 2024)

The importance of developmental programming in the beef industry - George A. Perry; Thomas H. Welsh (Animal Reproduction Science, 2024)

Quantification of CD3, FoxP3, and granzyme B immunostaining in canine renal cell carcinoma - Ashleigh Cournoyer; Hayley Amerman; Charles-Antoine Assenmacher; Amy Durham; James A. Perry; Allison Gedney; Nicholas Keuler; Matthew J. Atherton; Jennifer A. Lenz (Veterinary Immunology and Immunopathology, 2024)

Sublimation and infrared spectral properties of ammonium cyanide - Perry A. Gerakines; Yukiko Y. Yarnall; Reggie L. Hudson (Icarus, 2024)

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

Developmental programming of the ovarian reserve in livestock - Robert A. Cushman; Vahid Akbarinejad; George A. Perry; Clay A. Lents (Animal Reproduction Science, 2024)

Impacts of large scale climate modes on the current and future bimodal wave climate of a semi-protected shallow gulf - Benjamin Perry; Bas Huisman; José A. A. Antolínez; Patrick A. Hesp; Graziela Miot da Silva (Frontiers in Marine Science, 2024)
The bimodal wave climate of the semi-protected shallow Gulf St Vincent in South Australia has been analyzed through a forty-year (1980-2020) wave hindcast and an investigation into the climatic drivers of wave climate anomalies is presented. The sea and swell partitions of the wave climate were modelled independently as well as using an integrated model with both partitions represented. The wave hindcast was validated against two wave buoys located off the coast of Adelaide’s metropolitan beaches and key wave parameter anomalies were calculated across the gulf. Teleconnections were investigated, and the Southern Annular Mode is found to have the strongest correlations to wave parameter anomalies while the Southern Oscillation Index and the Dipole Mode Index fluctuations are found to correlate seasonally with wave parameter anomalies. Projected future trends of these climate drivers from literature have been related to the teleconnections found in this study to inform future trends of bimodal wave conditions in the gulf. The Southern Annular Mode is projected to trend positive which will reduce wave height and the westerly component of waves in the gulf, while the Southern Oscillation Index is projected to become more variable in the future which will lead to more extreme winter and spring wave conditions. An understanding of these trends allows coastal managers to pre-emptively manage the impacts of waves on the coastline at a seasonal to annual basis and provides insight into future wave conditions beyond these time periods.

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Mid-season drain severity impacts on rice yields, greenhouse gas emissions and heavy metal uptake in grain: evidence from on-farm studies - Henry Perry; Daniela R. Carrijo; Aria H. Duncan; Scott Fendorf; Bruce A. Linquist (Field Crops Research, 2024)

Capitalizing on skin in orthotics design: the effects of texture on plantar intrinsic foot muscles during locomotion - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

Brodie, a Dual-Purpose Chipping and Tablestock Variety with Resistance to Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode and Partial Resistance to Pathotype Pa2/3 of the Pale Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Louise-Marie Dandurand; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2024)

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

The topographical attenuation of cutaneous input is modulated at the ankle joint during gait - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

A cloudy forecast for species distribution models: Predictive uncertainties abound for California birds after a century of climate and land‐use change - John D. J. Clare; Perry de Valpine; Diana A. Moanga; Morgan W. Tingley; Steven R. Beissinger (Global Change Biology, 2024)
Correlative species distribution models are widely used to quantify past shifts in ranges or communities, and to predict future outcomes under ongoing global change. Practitioners confront a wide range of potentially plausible models for ecological dynamics, but most specific applications only consider a narrow set. Here, we clarify that certain model structures can embed restrictive assumptions about key sources of forecast uncertainty into an analysis. To evaluate forecast uncertainties and our ability to explain community change, we fit and compared 39 candidate multi‐ or joint species occupancy models to avian incidence data collected at 320 sites across California during the early 20th century and resurveyed a century later. We found massive (>20,000 LOOIC) differences in within‐time information criterion across models. Poorer fitting models omitting multivariate random effects predicted less variation in species richness changes and smaller contemporary communities, with considerable variation in predicted spatial patterns in richness changes across models. The top models suggested avian environmental associations changed across time, contemporary avian occupancy was influenced by previous site‐specific occupancy states, and that both latent site variables and species associations with these variables also varied over time. Collectively, our results recapitulate that simplified model assumptions not only impact predictive fit but may mask important sources of forecast uncertainty and mischaracterize the current state of system understanding when seeking to describe or project community responses to global change. We recommend that researchers seeking to make long‐term forecasts prioritize characterizing forecast uncertainty over seeking to present a single best guess. To do so reliably, we urge practitioners to employ models capable of characterizing the key sources of forecast uncertainty, where predictors, parameters and random effects may vary over time or further interact with previous occurrence states.

Distinctive hospital and community resistomes in Scottish urban wastewater: Metagenomics of a paired wastewater sampling design - Hannah C. Lepper; Meghan R. Perry; Bryan A. Wee; David Wills; Hanne Nielsen; Saria Otani; Moray Simon; Frank M. Aarestrup; Mark E.J. Woolhouse; Bram A.D. van Bunnik (Science of The Total Environment, 2023)

Careful plant choice can deliver more biodiverse vertical greening (green façades) - A. Salisbury; T. Blanusa; H. Bostock; J.N. Perry (Urban Forestry & Urban Greening, 2023)

Sudden death after a bite by a lowland swamp viper (Proatheris superciliaris) in Malawi: Dying of fright? - Beth A. Tippett Barr; Gary Brown; Mike Perry; Renee Ridzon; David A. Warrell (Toxicon, 2023)

Sea level rise adaptation pushes an insular endemic rodent closer to extinction - Paul J. Taillie; Sandra Sneckenberger; Neil Perry; Chad Anderson; Kevin Kalasz; Robert A. McCleery (Biodiversity and Conservation, 2023)
Understanding how species will respond to a rapidly changing global climate is requisite to conserving biodiversity. Though habitat losses from human development and land use change remain the most critical threats to biodiversity globally, some regions, such as low-lying islands, are particularly vulnerable to the effects of climate change. Despite this vulnerability, there may be opportunities for imperiled species on islands to adapt to the effects of climate-induced sea level rise. To understand how the response to rising seas may influence the amount of future habitat, we investigated shifts in the elevational range of the endangered silver rice rat ( Oryzomys palustris natator; hereafter “rice rat”), a species endemic to tidal environments of the Lower Florida Keys, USA. We quantified fine-scale habitat use using radio telemetry of collared animals, first in 2004, and again in 2021, thus spanning a 17-year period during which the local sea level rose by 0.142 m. We observed a shift in the elevational range limits of rice rats which closely mirrored the rise in sea level, and that this apparent ability to adapt to rising sea level decreased the extent of habitat loss in subsequent decades. However, over longer time scales (~ 100 yrs), the extent of habitat loss from sea level rise outpaced rice rats’ ability to adapt. As such, the conservation of biodiversity on low-lying islands hinges on the ability of the global community to decrease anthropogenic greenhouse gas emissions and mitigate the associated consequences for the global climate. Otherwise, conservation practitioners will be increasingly forced to make difficult decisions about how to conserve imperiled species on low-lying islands.

The Atlantic salmon's (Salmo salar) incremental thermal maximum is a more relevant and sensitive indicator of family-based differences in upper temperature tolerance than its critical thermal maximum - Eric H. Ignatz; Rebeccah M. Sandrelli; Émile Vadboncoeur; Fábio S. Zanuzzo; Guy M.L. Perry; Matthew L. Rise; A. Kurt Gamperl (Aquaculture, 2023)

Excitable systems: A new perspective on the cellular impact of elongate mineral particles - Shuyao Gu; Abby Bull; Jeneh K. Perry; Amilee Huang; Matt J. Hourwitz; Mona Abostate; John T. Fourkas; Andrey A. Korchevskiy; Ann G. Wylie; Wolfgang Losert (Environmental Research, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

A cross-sectional analysis of ambient fine particulate matter (PM2.5) exposure and haemoglobin levels in children aged under 5 years living in 36 countries - Daniel B. Odo; Ian A. Yang; Sagnik Dey; Melanie S. Hammer; Aaron van Donkelaar; Randall V. Martin; Guang-Hui Dong; Bo-Yi Yang; Perry Hystad; Luke D. Knibbs (Environmental Research, 2023)

Functional near infrared spectroscopy detects cortical activation changes concurrent with memory loss in postmenopausal women with Type II Diabetes - Stacey L. Gorniak; Victoria E. Wagner; Kelly Vaughn; Jonathan Perry; Lauren Gulley Cox; Hidetaka Hibino; Samuel A. Montero-Hernandez; Arturo E. Hernandez; Luca Pollonini (Experimental Brain Research, 2023)

Drivers of Ecological Condition Identify Bright Spots and Sites for Management Across Coastal Seascapes - Ben L. Gilby; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Jesse D. Mosman; Andrew D. Olds; Hannah J. Perry (Estuaries and Coasts, 2023)
Disentangling natural and anthropogenic effects on ecosystem condition can uncover bright spots in urban landscapes that are performing above expectations and so are potential sites for conservation or benchmarking, as well as sites performing below expectations that should be the focus of management. In this study, we tested for correlations between metrics indexing ecological condition (focusing on habitat-forming species) and a suite of spatial and environmental variables at 373 sites across four ecosystems (mangroves, seagrass, saltmarsh and rocky outcrops) and 13 estuaries in southeast Queensland, Australia. Ten condition metrics across the four ecosystems correlated with variables indexing the seascape context of sites, with condition metrics typically higher at sites more connected to natural features including the estuary mouth and mangroves. Urbanisation affected only two metrics, with rocky outcrop oyster cover being 75% lower at sites near extensive urbanisation and algae cover being highest at sites with intermediate urbanisation. We identified patterns in at least two variables from each ecosystem, meaning that decisions need to be made regarding optimal ecosystem states. Overall, management sites were more common than bright spots, with 50% more management sites in mangroves, 42.8% more in seagrasses, 38.5% more in saltmarshes and no bright spots in rocky outcrops (however, 10.3% of rocky outcrop sites were bright spots under an alternate ecosystem state model). We found that patterns in habitat condition across coastal seascapes can be predicted using spatial modelling approaches, and that these models can be readily used to prioritise management actions across the entire regions.

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Understanding coastal social values through citizen science: The example of Coastsnap in Western Australia - Carmen E. Elrick-Barr; Julian Clifton; Michael Cuttler; Craig Perry; Abbie A. Rogers (Ocean & Coastal Management, 2023)

Infrared spectra and optical constants of astronomical ices: V. cyclopropane and ethylene oxide - Reggie L. Hudson; Perry A. Gerakines; Yukiko Y. Yarnall (Icarus, 2023)

Lehigh, a Variety with Yellow Flesh and Resistance to the Golden Cyst Nematode and Common Scab - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2023)

Coexistence between similar invaders: The case of two cosmopolitan exotic insects - Matthew B. Arnold; Michael Back; Michael Daniel Crowell; Nageen Farooq; Prashant Ghimire; Omon A. Obarein; Kyle E. Smart; Trixie Taucher; Erin VanderJeugdt; Kayla I. Perry; Douglas A. Landis; Christie A. Bahlai (Ecology, 2023)
Biological invasions are usually examined in the context of their impacts on native species. However, few studies have examined the dynamics between invaders when multiple exotic species successfully coexist in a novel environment. Yet, long‐term coexistence of now established exotic species has been observed in North American lady beetle communities. Exotic lady beetles Harmonia axyridis and Coccinella septempunctata were introduced for biological control in agricultural systems and have since become dominant species within these communities. In this study, we investigated coexistence via spatial and temporal niche partitioning among H. axyridis and C. septempunctata using a 31‐year data set from southwestern Michigan, USA. We found evidence of long‐term coexistence through a combination of small‐scale environmental, habitat, and seasonal mechanisms. Across years, H. axyridis and C. septempunctata experienced patterns of cyclical dominance likely related to yearly variation in temperature and precipitation. Within years, populations of C. septempunctata peaked early in the growing season at 550 degree days, while H. axyridis populations grew in the season until 1250 degree days and continued to have high activity after this point. C. septempunctata was generally most abundant in herbaceous crops, whereas H. axyridis did not display strong habitat preferences. These findings suggest that within this region H. axyridis has broader habitat and abiotic environmental preferences, whereas C. septempunctata thrives under more specific ecological conditions. These ecological differences have contributed to the continued coexistence of these two invaders. Understanding the mechanisms that allow for the coexistence of dominant exotic species contributes to native biodiversity conservation management of invaded ecosystems.

Reprint of: COVID-19 messaging in U.S. state parks: Extensions of the outdoor recreation strategies and practices framework unmasked by the pandemic - Elizabeth E. Perry; Kimberly J. Coleman; Tatiana A. Iretskaia; Jordan M. Baer; Liesl F. Magnus; Peter R. Pettengill (Journal of Outdoor Recreation and Tourism, 2023)

Identifying optimal values of coastal habitat condition for management and restoration - Hannah J. Perry; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Andrew D. Olds; Jesse D. Mosman; Ben L. Gilby (Estuarine, Coastal and Shelf Science, 2023)

Correlating the role of nanofillers with active layer properties and performance of thin-film nanocomposite membranes - Lamar A. Perry; Nick Guan Pin Chew; Kasia Grzebyk; Pinar Cay-Durgun; Mary Laura Lind; Paban Sitaula; Mustapha Soukri; Orlando Coronell (Desalination, 2023)

Correction to: Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)

Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)
Pumas ( Puma concolor ) were eliminated from most of the eastern USA a century ago. In the past couple of decades, their recovery in the West has increased puma dispersal into the Midwest, with some individuals even traveling to the East Coast. We combined published expert opinion data and a habitat suitability index in an analysis that identified 17 areas in the Upper Midwest, Ozarks, Appalachia, and New England that could potentially host puma populations in the future. Thirteen of these were larger than 10,000 km 2 and so likely to ensure a puma population’s long-term genetic health. Further, we quantified patch size, human density, livestock density, percent public land, and a sociocultural index reflecting wildlife values for comparing patches, as well as present a summary of current legislation relevant to puma management in the East. Our work may be useful in identifying suitable areas to restore pumas based not only on the quality of their biophysical habitat, but also on social values conducive to puma-human coexistence.

Influence of corn supplementation to beef cows during mid- to late-gestation: Supplementation decreases placental microvascular surface density but does not alter uterine blood flow or neonatal performance1 - A.R. Tanner; M.L. Bauer; K.C. Swanson; V.C. Kennedy; J.D. Kirsch; J. Gaspers; N. Negrin-Pereira; A.B.P. Fontoura; G.A. Perry; G. Stokka; A. Rodas-Gonzalez; A. Ward; et al. (Livestock Science, 2023)

Seasonal differences in day-roost selection by Northern long-eared bats (Myotis septentrionalis) in Louisiana and a meta-analytical comparison across North America - Carlos J. Garcia; David A. Ray; Roger W. Perry; Richard D. Stevens (Forest Ecology and Management, 2023)

A cross-sectional analysis of long-term exposure to ambient air pollution and cognitive development in children aged 3–4 years living in 12 low- and middle-income countries - Daniel B. Odo; Ian A. Yang; Sagnik Dey; Melanie S. Hammer; Aaron van Donkelaar; Randall V. Martin; Guang-Hui Dong; Bo-Yi Yang; Perry Hystad; Luke D. Knibbs (Environmental Pollution, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

The American Lobster Settlement Index: History, lessons, and future of a long-term, transboundary monitoring collaborative - M. Conor McManus; Damian C. Brady; Curtis Brown; Joshua T. Carloni; Melanie Giffin; Andrew G. Goode; Kristyn Kleman; Peter Lawton; Arnault Le Bris; Scott Olszewski; Derek N. Perry; Rémy Rochette; et al. (Frontiers in Marine Science, 2023)
Understanding the processes that influence recruitment variability in marine populations has been a long-standing challenge for resource management. Quantifying abundance at early life stages for marine fish and invertebrates with complex life histories can be difficult and require unconventional sampling approaches. However, the benefit of developing appropriate tools to sample early life stages is that, together with associated demographic and environmental information, the data can provide insights into the causes and consequences of recruitment variability, allowing prediction of older life stage abundance. Before the 1980s, the earliest benthic life stages of the American lobster ( Homarus americanus ) eluded quantitative field surveys. With the development of diver-based and vessel-deployed sampling methods over the past three decades, the American Lobster Settlement Index (ALSI) program has expanded into a regional, transboundary commitment to better understand lobster settlement processes and forecast future fishery trends for what has become the most valuable single-species fishery in North America. In this context, “settlement” is a shorthand for the annual recruitment of young-of-year lobster to coastal nurseries, as postlarvae settle to the seabed at the end of larval development. Here, we review the development and products of the ALSI program, first outlining the goals, methods, and data products of the program. We then highlight how the program has advanced the scientific knowledge on pre- and post-settlement processes that influence the fate of a cohort from egg hatch to harvest, which provides insight into the spawner-recruit relationship. Lastly, we provide guidance for future research recommendations building on the ALSI science to-date, some major elements of the program that have allowed for its success, and considerations for maintaining the ALSI program. By highlighting the uniqueness and contributions of the ALSI program, we hope it serves as a model for other scientists, managers, and industry collaborators aiming to understand recruitment processes for species over a broad geographic area.

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Diné-centered research reframes the Gold King Mine Spill: Understanding social and spiritual impacts across space and time - Rebecca J. Clausen; Carmenlita Chief; Nicolette I. Teufel-Shone; Manley A. Begay; Perry H. Charley; Paloma I. Beamer; Nnenna Anako; Karletta Chief (Journal of Rural Studies, 2023)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

The effect of texture under distinct regions of the foot sole on human locomotion - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2022)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Caribbean king crab larvae and juveniles show tolerance to ocean acidification and ocean warming - Philip M. Gravinese; Shelby A. Perry; Angelo Jason Spadaro; Albert E. Boyd; Ian C. Enochs (Marine Biology, 2022)
Coastal habitats are experiencing decreases in seawater pH and increases in temperature due to anthropogenic climate change. The Caribbean king crab, Maguimithrax spinosissimus , plays a vital role on Western Atlantic reefs by grazing macroalgae that competes for space with coral recruits. Therefore, identifying its tolerance to anthropogenic stressors is critically needed if this species is to be considered as a potential restoration management strategy in coral reef environments. We examined the effects of temperature (control: 28 °C and elevated: 31 °C) and pH (control: 8.0 and reduced pH: 7.7) on the king crab’s larval and early juvenile survival, molt-stage duration, and morphology in a fully crossed laboratory experiment. Survival to the megalopal stage was reduced (13.5% lower) in the combined reduced pH and elevated temperature treatment relative to the control. First-stage (J1) juveniles delayed molting by 1.5 days in the reduced pH treatment, while second-stage (J2) crabs molted 3 days earlier when exposed to elevated temperature. Juvenile morphology did not differ among treatments. These results suggests that juvenile king crabs are tolerant to changes associated with climate change. Given the important role of the king crab as a grazer of macroalgae, its tolerance to climate stressors suggests that it could benefit restoration efforts aimed at making coral reefs more resilient to increasingly warm and acidic oceans into the future.

Gelatinous and soft-bodied zooplankton in the Northeast Pacific Ocean: Phosphorus content and potential resilience to phosphorus limitation - Florian Lüskow; Moira D. Galbraith; Brian P. V. Hunt; R. Ian Perry; Maarten Boersma; Evgeny A. Pakhomov (Hydrobiologia, 2022)

Annotated expression and activity data for murine recombinase alleles and transgenes: the CrePortal resource - Michelle N. Perry; Constance M. Smith; Hiroaki Onda; Martin Ringwald; Stephen A. Murray; Cynthia L. Smith (Mammalian Genome, 2022)
Recombinase alleles and transgenes can be used to facilitate spatio-temporal specificity of gene disruption or transgene expression. However, the versatility of this in vivo recombination system relies on having detailed and accurate characterization of recombinase expression and activity to enable selection of the appropriate allele or transgene. The CrePortal ( http://www.informatics.jax.org/home/recombinase ) leverages the informatics infrastructure of Mouse Genome Informatics to integrate data from the scientific literature, direct data submissions from the scientific community at-large, and from major projects developing new recombinase lines and characterizing recombinase expression and specificity patterns. Searching the CrePortal by recombinase activity or specific recombinase gene driver provides users with a recombinase alleles and transgenes activity tissue summary and matrix comparison of gene expression and recombinase activity with links to generation details, a recombinase activity grid, and associated phenotype annotations. Future improvements will add cell type-based activity annotations. The CrePortal provides a comprehensive presentation of recombinase allele and transgene data to assist researchers in selection of the recombinase allele or transgene based on where and when recombination is desired.

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Park Visitors’ Place Attachment and Climate Change-related Displacement: Potential Shifts in Who, Where, and When - Elizabeth E. Perry; Xiao Xiao; John M. Nettles; Tatiana A. Iretskaia; Robert E. Manning (Environmental Management, 2021)

Spatiotemporal patterns of ENSO‐precipitation relationships in the tropical Andes of southern Peru and Bolivia - Joseph A. Jonaitis; L. Baker Perry; Peter T. Soulé; Christopher Thaxton; Marcos F. Andrade‐Flores; Tania Ita Vargas; Laura Ticona (International Journal of Climatology, 2021)
Precipitation in the outer tropical Andes is highly seasonal, exhibits considerable interannual variability, and is vital for regulating freshwater availability, flooding, glacier mass balance, and droughts. The primary driver of interannual variability is El Niño Southern Oscillation (ENSO), with most investigations reporting that the El Niño (La Niña) results in negative (positive) precipitation anomalies across the region. Recent investigations, however, have identified substantial spatiotemporal differences in ENSO‐precipitation relationships. Motivated by the dissimilarity of these findings, this study examines a carefully selected data set (≥ 90% completeness) of ground‐based precipitation observations from 75 high‐elevation (≥ 2,500 m above sea level) meteorological stations in the tropical Andes of southern Peru and Bolivia for the period 1972–2016. Distinct groups of stations and associated variability in precipitation characteristics (e.g., total seasonal precipitation, wet season onset, and wet season length) are identified. Using no spatial constraints, the K‐Means algorithm optimally grouped stations into five easily identifiable groups. The groups farthest from the Amazon basin had significant negative (positive) precipitation anomalies ( p

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

Characterisation of LV myocardial exercise function by 2-D strain deformation imaging in elite adolescent footballers - Guido E. Pieles; Lucy Gowing; Diane Ryding; Dave Perry; Steven R. McNally; A. Graham Stuart; Craig A. Williams (European Journal of Applied Physiology, 2021)
Purpose Few data exist on the descriptions of LV myocardial mechanics and reserve during dynamic exercise of adolescent athletes. The aim of this study was to describe the LV myocardial and cardiopulmonary changes during exercise using 2-D strain deformation imaging. Methods Elite adolescent male football players ( n = 42) completed simultaneous cardiopulmonary exercise testing (CPET) and exercise echocardiography measurement of LV myocardial deformation by 2-D strain imaging. LV longitudinal and circumferential 2-D strain and strain rates were analyzed at each stage during incremental exercise to a work rate of 150 W. Additionally, exercise LV myocardial deformation and its relation to metabolic exercise parameters were evaluated at each exercise stage and in recovery using repeated measures ANOVA, linear regression and paired t tests. Results LV peak systolic baseline 2-D strain (longitudinal: − 15.4 ± 2.5%, circumferential: − 22.5 ± 3.1%) increased with each exercise stage, but longitudinal strain plateaued at 50 W (mean strain reserve − 7.8 ± 3.0) and did not significantly increase compared to subsequent exercise stages ( P > 0.05), whilst circumferential strain (mean strain reserve − 11.6 ± 3.3) significantly increased ( P < 0.05) throughout exercise up to 150 W as the dominant mechanism of exercise LV contractility increase. Regression analyses showed LV myocardial strain increased linearly relative to HR, VO 2 and O 2 pulse ( P < 0.05) for circumferential deformation, but showed attenuation for longitudinal deformation. Conclusion This study describes LV myocardial deformation dynamics by 2-D strain and provides reference values for LV myocardial strain and strain rate during exercise in adolescent footballers. It found important differences between LV longitudinal and circumferential myocardial mechanics during exercise and introduces a methodology that can be used to quantify LV function and cardiac reserve during exercise in adolescent athletes.

Waneta, a Variety with Excellent Chip Color out of Cold Storage, Long Tuber Dormancy, and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Fungal communities living within leaves of native Hawaiian dicots are structured by landscape‐scale variables as well as by host plants - John L. Darcy; Sean O. I. Swift; Gerald M. Cobian; Geoffrey L. Zahn; Brian A. Perry; Anthony S. Amend (Molecular Ecology, 2020)
A phylogenetically diverse array of fungi live within healthy leaf tissue of dicotyledonous plants. Many studies have examined these endophytes within a single plant species and/or at small spatial scales, but landscape‐scale variables that determine their community composition are not well understood, either across geographic space, across climatic conditions, or in the context of host plant phylogeny. Here, we evaluate the contributions of these variables to endophyte beta diversity using a survey of foliar endophytic fungi in native Hawaiian dicots sampled across the Hawaiian archipelago. We used Illumina technology to sequence fungal ITS1 amplicons to characterize foliar endophyte communities across five islands and 80 host plant genera. We found that communities of foliar endophytic fungi showed strong geographic structuring between distances of 7 and 36 km. Endophyte community structure was most strongly associated with host plant phylogeny and evapotranspiration, and was also significantly associated with NDVI, elevation and solar radiation. Additionally, our bipartite network analysis revealed that the five islands we sampled each harboured significantly specialized endophyte communities. These results demonstrate how the interaction of factors at large and small spatial and phylogenetic scales shapes fungal symbiont communities.

Temperature–Induced Hatch Failure and Nauplii Malformation in Antarctic Krill - Frances A. Perry; So Kawaguchi; Angus Atkinson; Sévrine F. Sailley; Geraint A. Tarling; Daniel J. Mayor; Cathy H. Lucas; R. King; A. Cooper (Frontiers in Marine Science, 2020)

Pharmacotherapy for the Pseudobulbar Affect in Individuals Who Have Sustained a Traumatic Brain Injury: a Systematic Review - Amelia J. Hicks; Fiona J. Clay; Jennie L. Ponsford; Luke A. Perry; Mahesh Jayaram; Rachel Batty; Malcolm Hopwood (Neuropsychology Review, 2020)

Early-earth nonprotein amino acid metabolites in modern cyanobacterial microbialites - Stephanie L. Bishop; Fiona J. M. Tymm; Karen Perry; Jeff K. Kerkovius; Frederic Menard; Allyson Brady; Greg Slater; Darlene S. S. Lim; James S. Metcalf; Sandra A. Banack; Paul A. Cox; Susan J. Murch (Environmental Chemistry Letters, 2020)

A randomized, placebo-controlled, phase 1 study to evaluate the effects of TAK-063 on ketamine-induced changes in fMRI BOLD signal in healthy subjects - Deborah A. Yurgelun-Todd; Perry F. Renshaw; Paul Goldsmith; Tolga Uz; Thomas A. Macek (Psychopharmacology, 2020)
Rationale Phosphodiesterase 10A inhibitor TAK-063 has shown effects that suggest efficacy in schizophrenia treatment. Objective This randomized, double-blind, placebo-controlled, incomplete-crossover study investigated effects of single oral administration of TAK-063 on ketamine-induced changes in blood oxygen level-dependent (BOLD) signal in healthy males. Methods Healthy men aged 18 to 45 years with normal magnetic resonance imaging (MRI) scans and electroencephalogram measurements at screening were eligible. Each subject was randomized to one of nine treatment schedules: all subjects received placebo and two of three doses of TAK-063 followed by ketamine. The primary endpoint was ketamine-induced brain activity in select regions of the brain during resting state. Secondary endpoints included pharmacokinetic parameters of TAK-063, proportion of subjects with treatment-emergent adverse events (AEs), and percentage of subjects meeting criteria for abnormal safety laboratory tests and vital sign measurements. Results The study comprised 27 subjects. Prior to ketamine infusion, TAK-063 exerted region-specific effects on resting state functional MRI (fMRI) BOLD signal. After ketamine administration, TAK-063 reduced the Cohen’s effect size for resting-state fMRI BOLD signal in key brain regions examined, and exerted similar effects on BOLD signal during the working memory task across all doses. TAK-063 was safe and well tolerated. Conclusions Our results are consistent with non-clinical studies of ketamine and TAK-063 and clinical studies of ketamine and risperidone. It is unknown whether these data are predictive of potential antipsychotic efficacy, and further analyses are required.

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Seasonal and diel patterns in activity and habitat use by brook trout (Salvelinus fontinalis) in a small Newfoundland lake - D. Cote; B. Tibble; R. A. Curry; S. Peake; B. K. Adams; K. D. Clarke; R. Perry (Environmental Biology of Fishes, 2020)
Despite the challenges winter poses to salmonids inhabiting temperate and northern environments, there are relatively few studies that evaluate the factors that influence activity and habitat use during this season, particularly for lake environments that are ice-covered. This study examines brook trout depth distribution and movement (activity and range) in relation to temperature, light, and time of day across a 17-month period in a small lake in Newfoundland, Canada. Brook trout maintained elevated diurnal activity patterns throughout the year, despite seasonal changes in temperature, shifts in depth use, and prolonged, ice-induced darkness. Despite the tendency for relatively lower activity at night, brook trout remained active nocturnally, inferring a shift in foraging modes rather than a cessation of feeding. Winter movement velocities and ranges were less than other seasons but they occupied littoral areas that overlapped extensively with spring and fall core ranges. In contrast, summer core ranges of brook trout were principally comprised of areas with cooler water in the deep portion of the lake. As water temperature increased, daytime movement velocities increased in a log-linear fashion, whereas modeled nighttime movement velocity relationships with temperature were curvilinear and included the lowest movement velocities at 2–3 °C and the highest at the extremes of the occupied temperature range. The ability of brook trout to maintain diurnal activity patterns throughout a wide spectrum of environmental conditions suggests a strong behavioral and physiological capacity to adapt to their seasonally variable environment.

Projected late 21st century changes to the regional impacts of the El Niño-Southern Oscillation - S. J. Perry; S. McGregor; A. Sen Gupta; M. H. England; N. Maher (Climate Dynamics, 2020)

Neurofibromatosis type 2 discordance in monozygous twins - S. Amico; P. Smith; S. Tobi; M. Perry; A. Wallace; D. G. Evans (Familial Cancer, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Calcium carbonate production by fish in temperate marine environments - Michael A. Salter; Chris T. Perry; Abigail M. Smith (Limnology and Oceanography, 2019)
Marine bony fishes are an important source of calcium carbonate with relevance to sediment production and inorganic carbon cycling. However, knowledge of the production and fate of these carbonates is based primarily on data from warm‐water reef fishes, with efforts to assess global‐scale implications constrained by assumptions that this small cross section of the global fish community is widely representative. Here we test the extent to which temperature influences fish carbonate mineralogy and morphology by comparing products from temperate settings (20 species at temperatures spanning 10–18°C) against existing data (23–27°C). Overall, carbonate products were mineralogically, compositionally, and morphologically similar throughout the thermal range, and in most cases, we observed no differences within species (18 vs. 24°C) or families (10 vs. 25°C). Confirmation of within‐family consistency over large thermal gradients is significant because: (1) it facilitates a substantial range expansion over which fish carbonate production models can be constructed, even where family‐level product data are geographically limited; and (2) it implies that the solubility of products from any given fish family varies only due to local carbonate saturation states at excretion (and not crystallographic differences). The only exception was in two members of the Labridae (wrasses), which produced low‐Mg calcite (LMC) and minor amorphous calcium–magnesium carbonate (ACMC) at 10°C; the inverse of products from confamilials at 25°C. This finding could have significant implications for understanding the role of fish carbonates globally because ACMC is a highly unstable carbonate polymorph, whereas LMC is very stable.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Census Estimates of Algal and Epiphytic Carbonate Production Highlight Tropical Seagrass Meadows as Sediment Production Hotspots - Chris T. Perry; Michael A. Salter; Kyle M. Morgan; Alastair R. Harborne (Frontiers in Marine Science, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Recurrent Hypoglycemia Exacerbates Cerebral Ischemic Damage in Diabetic Rats via Enhanced Post-Ischemic Mitochondrial Dysfunction - Vibha Shukla; Perry Fuchs; Allen Liu; Charles H. Cohan; Chuanhui Dong; Clinton B. Wright; Miguel A. Perez-Pinzon; Kunjan R. Dave (Translational Stroke Research, 2019)

Carbon dioxide enrichment alters predator avoidance and sex determination but only sex is mediated by GABAA receptors - Jean-Claude Abboud; Edgar A. Bartolome; Mayra Blanco; Annalise C. Kress; Ian Y. Ellis; Perry K. Yazzolino; Kamrin I. Sorensen; James R. Winslow; David A. Cleary; Hugh Lefcort (Hydrobiologia, 2019)

A test of top-down control on plant production and nutrient quality in low-salinity tidal marshes - Lori A. Sutter; Randy M. Chambers; Madeline Karp; James E. Perry (Aquatic Sciences, 2019)

Winter climate variability in the southern Appalachian Mountains, 1910–2017 - Montana A. Eck; L. Baker Perry; Peter T. Soulé; Johnathan W. Sugg; Douglas K. Miller (International Journal of Climatology, 2019)
Located in the mid‐latitudes and exhibiting the greatest topographic relief in the eastern United States, the southern Appalachian Mountains (SAM) contain some of the most diverse climatological environments in the United States. This diversity is most pronounced in the winter season when temperature and snowfall can vary drastically across the region. In this study, we identify long‐term trends and variation of temperature and snowfall in the SAM of the southeastern United States during climatological winter (DJF) from 1910 to 2017. Along with recognizing statistically significant climatic trends, we also identify the influence of several teleconnection patterns, namely the El Niño‐Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Pacific Decadal Oscillation (PDO) that further scientific understanding of how this region has remained a climatic anomaly. Results of this study indicate the SAM have experienced a statistically significant long‐term cooling trend since the early 20th century, with recent decades suggesting a reversal towards a warming pattern. Snowfall exhibited high interannual variability, with the 1960s and 1970s producing anomalously high amounts of snowfall. Several atmospheric forcing couplings are identified that align with anomalous conditions in the region. Most notably, negative temperature anomalies and higher snowfall amounts were frequently found during El Niño and negative NAO seasons, with the opposite being true during La Niña and positive NAO winters. The influence of these teleconnection patterns was spatially dependent, with lower elevations and eastern‐facing slopes being highly dependent on the phase of ENSO for snowfall, whereas higher elevations and western‐facing slopes were more reliant on the NAO. The identification of pattern couplings is critical to improving understanding of the anomalous climate of the SAM, enhancing seasonal forecasting, and predicting future climate change in the region.

Evaluation of a traditional Māori harvesting method for sampling kōura (freshwater crayfish, Paranephrops planifrons ) and toi toi (bully, Gobiomorphus spp.) populations in two New Zealand streams - Ian A. Kusabs; Brendan J. Hicks; John M. Quinn; William L. Perry; Hēmi Whaanga (New Zealand Journal of Marine and Freshwater Research, 2018)
Representative sampling of crayfish in streams is often impractical, especially in non‐wadable habitats, or in areas with soft substrates. Whakaweku are artificial habitats made from bracken fern ( Pteridium esculentum ) that can be used successfully in a range of habitats. We compared whakaweku, minnow traps, fyke nets and electrofishing for sampling freshwater crayfish (kōura; Paranephrops planifrons ) and bullies (toi toi; Gobiomorphus spp .) in two streams with differing stream characteristics and fish assemblages. Whakaweku captured a full‐size range of kōura of both sexes, including small kōura (OCL 7–12 mm) that were not caught by minnow traps or fyke nets. Colonisation by kōura reached 90% of maximum after 2 weeks and CPUE was constant from 2 to 9 weeks. After 9 weeks, CPUE decreased due to decay of the fern fronds. Whakaweku are an effective sampling tool that are inexpensive, simple to set, and do not require expensive equipment or specialised training.

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

A century of climate and land‐use change cause species turnover without loss of beta diversity in California’s Central Valley - Sarah A. MacLean; Andrea F. Rios Dominguez; Perry de Valpine; Steven R. Beissinger (Global Change Biology, 2018)
Climate and land‐use changes are thought to be the greatest threats to biodiversity, but few studies have directly measured their simultaneous impacts on species distributions. We used a unique historic resource—early 20th‐century bird surveys conducted by Joseph Grinnell and colleagues—paired with contemporary resurveys a century later to examine changes in bird distributions in California's Central Valley, one of the most intensively modified agricultural zones in the world and a region of heterogeneous climate change. We analyzed species‐ and community‐level occupancy using multispecies occupancy models that explicitly accounted for imperfect detection probability, and developed a novel, simulation‐based method to compare the relative influences of climate and land‐use covariates on site‐level species richness and beta diversity (measured by Jaccard similarity). Surprisingly, we show that mean occupancy, species richness and between‐site similarity have remained remarkably stable over the past century. Stability in community‐level metrics masked substantial changes in species composition; occupancy declines of some species were equally matched by increases in others, predominantly species with generalist or human‐associated habitat preferences. Bird occupancy, richness and diversity within each era were driven most strongly by water availability (precipitation and percent water cover), indicating that both climate and land‐use are important drivers of species distributions. Water availability had much stronger effects than temperature, urbanization and agricultural cover, which are typically thought to drive biodiversity decline.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Nitrogen isotope (δ 15 N) patterns for amino acids in lemur bones are inconsistent with aridity driving megafaunal extinction in south‐western Madagascar - Sean W. Hixon; Emma A. Elliott Smith; Brooke E. Crowley; George H. Perry; Jeannot Randrianasy; Jean Freddy Ranaivoarisoa; Douglas J. Kennett; Seth D. Newsome (Journal of Quaternary Science, 2018)
Most endemic species with body masses >10 kg on Madagascar went extinct within the past 1000 years. The extent to which human predation, anthropogenic landscape transformation and aridification may separately or together explain this extinction pattern remains controversial. We present nitrogen isotope (δ 15 N) values of individual amino acids preserved in bones from now‐extinct Pachylemur insignis and extant Propithecus verreauxi from two subfossil sites in south‐western Madagascar: Tsirave and Taolambiby. The amino acid‐specific approach allows us to identify environmental signals that are otherwise difficult to recognize in bulk collagen δ 15 N values. Specifically, we use the δ 15 N values of source amino acids (phenylalanine and lysine) as a proxy for habitat aridity between ca . 4000 years ago and present and the spacing of δ 15 N values between trophic and source amino acids to quantify trophic levels for these two lemur species. Despite paleoenvironmental evidence for lowering water tables and the expansion of relatively arid savanna between 4000 and 1000 years ago, our isotope data suggest that these lemurs did not live in increasingly arid habitats and did not change their trophic level. Together, our results support the hypothesis that aridity alone did not play a major role in late Holocene megafaunal extinctions in south‐western Madagascar.

Multiple abiotic factors correlate with parallel evolution in Australian soil burrowing cockroaches - Perry G. Beasley‐Hall; Timothy R. C. Lee; Harley A. Rose; Nathan Lo (Journal of Biogeography, 2018)
Aim The ways in which abiotic factors contribute to parallel evolution—the evolution of similar, derived phenotypes in independent, closely related lineages—remain understudied. Australian cockroaches of the subfamilies Panesthiinae (“wood feeders”) and Geoscapheinae (“soil burrowers”) are two closely related groups that provide a striking example of parallel evolution of burrowing behaviour. The ancestral wood‐feeding panesthiines migrated from Asia ~20 million years ago before soil burrowing was independently acquired multiple times in the derived geoscapheines. Here, we investigate whether specific abiotic factors were associated with the parallel evolution of soil burrowing behaviour, and whether divergence events of geoscapheines from panesthiine ancestors are consistent with niche conservatism or divergence. Location The Australian mainland, including the areas in which selected Australian Panesthiinae and Geoscapheinae cockroach species are distributed. Methods We generated environmental niche models for members of the Australian Geoscapheinae and Panesthiinae using presence‐only data and abiotic variables related to temperature, precipitation, and soil composition from BioClim and the Australian Soil Resource Information System. We used an existing phylogenetic framework to compare environmental niche models and tested for niche conservatism versus divergence. Morphological convergence was assessed by a regression analysis and principal components analysis of leg segment and body dimensions in soil burrowers and wood feeders. Results We found no relationship between niche similarity and time since divergence, and only limited evidence for phylogenetic signal with respect to the environmental variables examined. We found that soil burrowing behaviour is consistently correlated with thirteen abiotic factors associated with aridity, including a wider range of temperatures and lower precipitation levels. Evidence for convergence in leg morphology and body dimensions across soil burrowers was found. Main conclusions Our results are consistent with soil burrowing behaviour evolving in response to ancient aridification events following the arrival of the Panesthiinae in Australia. Our results suggest a scenario of niche divergence between soil burrowers and each of their wood feeding sister taxa. There is evidence for morphological convergence on a “shovel‐like” protibiotarsus in the Geoscapheinae that would aid in burrowing into soil.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Habitat Connectivity of Fish in Temperate Shallow-Water Seascapes - Diana Perry; Thomas A. B. Staveley; Martin Gullström (Frontiers in Marine Science, 2018)

First global molecular phylogeny and biogeographical analysis of two arachnid orders (Schizomida and Uropygi) supports a tropical Pangean origin and mid‐Cretaceous diversification - Ronald M. Clouse; Michael G. Branstetter; Perry Buenavente; Louise M. Crowley; Jesse Czekanski‐Moir; David Emmanuel M. General; Gonzalo Giribet; Mark S. Harvey; Daniel A. Janies; Alma B. Mohagan; Dave P. Mohagan; Prashant P. Sharma; et al. (Journal of Biogeography, 2017)
Aim We sought to illuminate the history of the arachnid orders Schizomida and Uropygi, neither of which have previously been subjected to global molecular phylogenetic and biogeographical analyses. Location Specimens used in this study were collected in all major tropical and subtropical areas where they are presently found, including the Americas, Africa, Australia and the Indo‐Pacific region. Methods From field‐collected specimens, we sequenced two nuclear and two mitochondrial markers, combined these with publicly available data, and conducted multi‐gene phylogenetic analyses on 240 Schizomida, 24 Uropygi and 12 other arachnid outgroups. Schizomid specimens included one specimen from the small family Protoschizomidae; other schizomid specimens were in Hubbardiidae, subfamily Hubbardiinae, which holds 289 of the order's 305 named species. We inferred ancestral areas using the Dispersal‐Extinction‐Cladogenesis model of range evolution, and we used fossil calibrations to estimate divergence times. Results We recovered monophyletic Schizomida and Uropygi as each other's sister group, forming the clade Thelyphonida, and terminals from the New World were usually positioned as the earliest diverging lineages. The ancestral area for schizomids reconstructed unambiguously to the region comprised of Mexico, Southern California and Florida (the xeric New World subtropics). Optimal trees suggested a single colonization of the Indo‐Pacific in both orders, although this did not receive bootstrap support. Molecular dating gave an Upper Carboniferous origin for each order, and a mid‐Cretaceous expansion of Schizomida, including the origin and initial diversification of those in the Indo‐Pacific. Main conclusions Ancestral area reconstructions, molecular dating and fossil evidence all support an Upper Carboniferous, tropical Pangean origin for Thelyphonida, Schizomida and perhaps Uropygi. Much of this region became unsuitable habitat for these arachnids during the breakup of Pangea, but they persisted in the area that is now Meso‐ and South America. From there they then expanded to the Indo‐Pacific, where schizomids today display an idiosyncratic combination of microendemism and long‐range dispersal.

Palaeoecological records of coral community development on a turbid, nearshore reef complex: baselines for assessing ecological change - J. A. Johnson; C. T. Perry; S. G. Smithers; K. M. Morgan; N. Santodomingo; K. G. Johnson (Coral Reefs, 2017)

High-resolution mapping reveals linkage between genes in common bean cultivar Ouro Negro conferring resistance to the rust, anthracnose, and angular leaf spot diseases - Giseli Valentini; Maria Celeste Gonçalves-Vidigal; Oscar P. Hurtado-Gonzales; Sandra Aparecida de Lima Castro; Perry B. Cregan; Qijian Song; Marcial A. Pastor-Corrales (Theoretical and Applied Genetics, 2017)

Strontium isotope evidence for long-distance immigration into the Byzantine port city of Aila, modern Aqaba, Jordan - Megan A. Perry; Cammie Jennings; Drew S. Coleman (Archaeological and Anthropological Sciences, 2017)

Nearshore Turbid-Zone Corals Exhibit High Bleaching Tolerance on the Great Barrier Reef Following the 2016 Ocean Warming Event - Kyle M. Morgan; Chris T. Perry; Jamie A. Johnson; Scott G. Smithers (Frontiers in Marine Science, 2017)

Associations of human skeletal muscle fiber type and insulin sensitivity, blood lipids, and vascular hemodynamics in a cohort of premenopausal women - Gordon Fisher; Samuel T. Windham; Perry Griffin; Jonathan L. Warren; Barbara A. Gower; Gary R. Hunter (European Journal of Applied Physiology, 2017)

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Lamoka, a Variety with Excellent Chip Color Out of Cold Storage and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2017)

Twenty years of ModelDB and beyond: building essential modeling tools for the future of neuroscience - Robert A. McDougal; Thomas M. Morse; Ted Carnevale; Luis Marenco; Rixin Wang; Michele Migliore; Perry L. Miller; Gordon M. Shepherd; Michael L. Hines (Journal of Computational Neuroscience, 2017)

Fresh Water Lens Persistence and Root Zone Salinization Hazard Under Temperate Climate - Sija F. Stofberg; Gualbert H. P. Oude Essink; Pieter S. Pauw; Perry G. B. de Louw; Anton Leijnse; Sjoerd E. A. T. M. van der Zee (Water Resources Management, 2017)

Attendance and nursing patterns of harp seals in the harsh environment of the northwest Atlantic - Elizabeth A. Perry; Garry B. Stenson; Alejandro D. Buren (Polar Biology, 2017)

Characterizing Movement of Ground-Dwelling Arthropods with a Novel Mark-Capture Method Using Fluorescent Powder - Kayla I. Perry; Kimberly F. Wallin; John W. Wenzel; Daniel A. Herms (Journal of Insect Behavior, 2017)

Do birds vocalize at higher pitch in noise, or is it a matter of measurement? - Alejandro A. Ríos-Chelén; Ambria N. McDonald; Ayala Berger; Anna C. Perry; Alan H. Krakauer; Gail L. Patricelli (Behavioral Ecology and Sociobiology, 2017)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Agrobacterium-mediated transformation of thin cell layer explants of Scutellaria ocmulgee small: a rare plant with anti-tumor properties - Brajesh N. Vaidya; Carissa L. Jackson; Zachary D. Perry; Sadanand A. Dhekney; Nirmal Joshee (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Linking innovative measurement technologies (ConMon and Dataflow© systems) for high-resolution temporal and spatial dissolved oxygen criteria assessment - C. A. O’Leary; E. Perry; A. Bayard; L. Wainger; W. R. Boynton (Environmental Monitoring and Assessment, 2016)

Density‐dependent resource selection by a terrestrial herbivore in response to sea‐to‐land nutrient transfer by seals - Philip D. McLoughlin; Kenton Lysak; Lucie Debeffe; Thomas Perry; Keith A. Hobson (Ecology, 2016)
Sea‐to‐land nutrient transfers can connect marine food webs to those on land, creating a dependence on marine webs by opportunistic species. We show how nitrogen, imported by gray seals, Halichoerus grypus , and traced through stable isotope (δ 15 N) measurements in marram grass , Ammophila breviligulata , significantly alters foraging behavior of a free‐roaming megaherbivore (feral horses, Equus ferus caballus ) on Sable Island, Canada. Values of δ 15 N correlated with protein content of marram and strongly related to pupping‐seal densities, and positively influenced selective foraging by horses. The latter was density dependent, consistent with optimal foraging theory. We present the first demonstration of how sea‐to‐land nutrient transfers can affect the behavioral process of resource selection (resource use relative to availability) of terrestrial consumers. We hypothesize that persistence of horses on Sable Island is being facilitated by N subsidies. Our results have relevance to advancing theory on trophic dynamics in island biogeography and metaecosystem ecology.

Fire–vegetation feedbacks and alternative states: common mechanisms of temperate forest vulnerability to fire in southern South America and New Zealand - T Kitzberger; GLW Perry; J Paritsis; JH Gowda; AJ Tepley; A Holz; TT Veblen (New Zealand Journal of Botany, 2016)
In the context of global warming and increasing impacts of invasive plants and animals, we examine how positive fire–vegetation feedbacks are increasing the vulnerability of pyrophobic temperate forests to conversion to pyrophytic non‐forest vegetation in southern South America and New Zealand. We extensively review the relevant literature to reveal how these temperate southern hemisphere floras have generated similar positive fire–vegetation feedback mechanisms resulting in increased vulnerability to anthropogenically altered fire regimens. For the two regions, we address the following questions. 1. What are the major plant species, physiognomic types and functional types characteristic of pyrophytic versus pyrophobic vegetation types and how do their traits affect flammability, resistance to fire and recovery after fire? 2. What are the roles of herbivory and microclimate in enhancing fire–vegetation feedbacks? 3. Are there similarities in trends of cover type transitions in relation to altered fire regimens? 4. How are climate change, land‐use trends and the effects of introduced plants and animals affecting the vulnerability of these ecosystems to fire‐induced transitions to alternative stable states? Most temperate forests of New Zealand and southern South America evolved under conditions of low fire frequencies so few taxa became adapted to recurrent fire. Current dichotomous landscapes consisting of juxtaposed pyrophobic and pyrophytic vegetation types are the outcome of the expansion of fire‐resilient and fire‐promoting species associated with the arrival of humans. Despite considerable differences in human history and biogeographic history, the case studies presented here show remarkable parallels in life‐history traits of the key pyrophobic taxa, fire–vegetation feedback mechanisms, overall ecosystem responses to anthropogenic alteration of fire regimens, and likely vulnerability to expected global change influences on future fire regimens.

Prediction of the Export and Fate of Global Ocean Net Primary Production: The EXPORTS Science Plan - David A. Siegel; Ken O. Buesseler; Michael J. Behrenfeld; Claudia R. Benitez-Nelson; Emmanuel Boss; Mark A. Brzezinski; Adrian Burd; Craig A. Carlson; Eric A. D'Asaro; Scott C. Doney; Mary J. Perry; Rachel H. R. Stanley; et al. (Frontiers in Marine Science, 2016)

Long-term dynamics of watershed leaching and lake sediment sequestration of rare earth elements following deglaciation of two mountain watersheds - Stephen A. Norton; Marie-Claire Pierret; Jiří Kopáček; Michael J. Handley; Randall H. Perry (Journal of Paleolimnology, 2016)

An Overview of Occupational Risks From Climate Change - Katie M. Applebaum; Jay Graham; George M. Gray; Peter LaPuma; Sabrina A. McCormick; Amanda Northcross; Melissa J. Perry (Current Environmental Health Reports, 2016)

Amphetamine increases activity but not exploration in humans and mice - Arpi Minassian; Jared W. Young; Zackary A. Cope; Brook L. Henry; Mark A. Geyer; William Perry (Psychopharmacology, 2016)

A systematic review of dietary, nutritional, and physical activity interventions for the prevention of prostate cancer progression and mortality - Lucy E. Hackshaw-McGeagh; Rachel E. Perry; Verity A. Leach; Sara Qandil; Mona Jeffreys; Richard M. Martin; J. Athene Lane (Cancer Causes & Control, 2015)

Legume, cropping intensity, and N-fertilization effects on soil attributes and processes from an eight-year-old semiarid wheat system - Justin K. O’Dea; Clain A. Jones; Catherine A. Zabinski; Perry R. Miller; Ilai N. Keren (Nutrient Cycling in Agroecosystems, 2015)

A model of skin inflammation in humans leads to a rapid and reproducible increase in the interferon response signature: a potential translational model for drug development - Marion C. Dickson; Valerie J. Ludbrook; Hayley C. Perry; Paul A. Wilson; Sam J. Garthside; Michael H. Binks (Inflammation Research, 2015)

Bacteria or melanosomes? A geochemical analysis of micro-bodies on a tadpole from the Oligocene Enspel Formation of Germany - Holly E. Barden; Uwe Bergmann; Nicholas P. Edwards; Victoria M. Egerton; Phillip L. Manning; Sarah Perry; Arjen van Veelen; Roy A. Wogelius; Bart E. van Dongen (Palaeobiodiversity and Palaeoenvironments, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Quantitative trait locus analysis of seed sulfur-containing amino acids in two recombinant inbred line populations of soybean - Xianzhi Wang; Guo-Liang Jiang; Qijian Song; Perry B. Cregan; Roy A. Scott; Jiaoping Zhang; Yang Yen; Michael Brown (Euphytica, 2015)

Developing and Evaluating Rapid Field Methods to Estimate Peat Carbon - Rodney A. Chimner; Cassandra A. Ott; Charles H. Perry; Randall K. Kolka (Wetlands, 2014)

Identification and validation of quantitative trait loci for seed yield, oil and protein contents in two recombinant inbred line populations of soybean - Xianzhi Wang; Guo-Liang Jiang; Marci Green; Roy A. Scott; Qijian Song; David L. Hyten; Perry B. Cregan (Molecular Genetics and Genomics, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Dietary Supplementation of Usnic Acid, an Antimicrobial Compound in Lichens, Does Not Affect Rumen Bacterial Diversity or Density in Reindeer - Trine Glad; Perry Barboza; Roderick I. Mackie; André-Denis G. Wright; Lorenzo Brusetti; Svein D. Mathiesen; Monica A. Sundset (Current Microbiology, 2014)

Neuronal failure in Alzheimer’s disease: a view through the oxidative stress looking-glass - David J. Bonda; Xinglong Wang; Hyoung-Gon Lee; Mark A. Smith; George Perry; Xiongwei Zhu (Neuroscience Bulletin, 2014)

Overlapping striatal sites mediate scopolamine-induced feeding suppression and mu-opioid-mediated hyperphagia in the rat - Michelle L. Perry; Wayne E. Pratt; Brian A. Baldo (Psychopharmacology, 2014)

Tidal Freshwater Marsh Plant Responses to Low Level Salinity Increases - Lori A. Sutter; James E. Perry; Randy M. Chambers (Wetlands, 2014)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Identities and distributions of the co-invading ectomycorrhizal fungal symbionts of exotic pines in the Hawaiian Islands - Nicole A. Hynson; Vincent S. F. T. Merckx; Brian A. Perry; Kathleen K. Treseder (Biological Invasions, 2013)

Improvements to Rapfish: a rapid evaluation technique for fisheries integrating ecological and human dimensions a - T. J. Pitcher; M. E. Lam; C. Ainsworth; A. Martindale; K. Nakamura; R. I. Perry; T. Ward (Journal of Fish Biology, 2013)
This paper reports recent developments in Rapfish, a normative, scalable and flexible rapid appraisal technique that integrates both ecological and human dimensions to evaluate the status of fisheries in reference to a norm or goal. Appraisal status targets may be sustainability, compliance with a standard (such as the UN code of conduct for responsible fisheries) or the degree of progress in meeting some other goal or target. The method combines semi‐quantitative ( e.g . ecological) and qualitative ( e.g . social) data via multiple evaluation fields, each of which is assessed through scores assigned to six to 12 attributes or indicators: the scoring method allows user flexibility to adopt a wide range of utility relationships. For assessing sustainability, six evaluation fields have been developed: ecological, technological, economic, social, ethical and institutional. Each field can be assessed directly with a set of scored attributes, or several of the fields can be dealt with in greater detail using nested subfields that themselves comprise multidimensional Rapfish assessments ( e.g . the hierarchical institutional field encompasses both governance and management, including a detailed analysis of legality). The user has the choice of including all or only some of the available sustainability fields. For the attributes themselves, there will rarely be quantitative data, but scoring allows these items to be estimated. Indeed, within a normative framework, one important advantage with Rapfish is transparency of the rigour, quality and replicability of the scores. The Rapfish technique employs a constrained multidimensional ordination that is scaled to situate data points within evaluation space. Within each evaluation field, results may be presented as a two‐dimensional plot or in a one‐dimensional rank order. Uncertainty is expressed through the probability distribution of Monte‐Carlo simulations that use the c.l . on each original observation. Overall results of the multidisciplinary analysis may be shown using kite diagrams that compare different locations, time periods (including future projections) and management scenarios, which make policy trade‐offs explicit. These enhancements are now available in the R programming language and on an open website, where users can run Rapfish analyses by downloading the software or uploading their data to a user interface.

Mechanisms underlying plant sexual dimorphism in multi‐trophic arthropod communities - William K. Petry; Kayla I. Perry; Aleshia Fremgen; Sarah K. Rudeen; Mitchell Lopez; John Dryburgh; Kailen A. Mooney (Ecology, 2013)
A growing body of research documents the importance of plant genetic effects on arthropod community structure. However, the mechanisms underlying these effects are often unclear. Additionally, plant genetic effects have largely been quantified in common gardens, thus inflating the estimates of their importance by minimizing levels of natural variation. Using Valeriana edulis , a dioecious plant with genetically based sex determination, we conducted surveys and experiments on wild‐grown individuals to document field patterns of arthropod association between the sexes and the mechanisms underlying these plant genetic effects. Three years of surveys revealed strong and consistent sex‐biased arthropod association in wild‐grown plants: female plants supported 4‐fold, 1.5‐fold, and 4‐fold higher densities of aphids, aphid predators, and aphid‐tending ants, respectively, compared to males. There was mixed evidence that the female bias for aphids was due to higher plant quality, while we found no difference between plant sexes in aphid preference or the top‐down effects of predators and tending ants. Female bias for ants was due to both the greater attractiveness of female plants (direct effect mediated by floral nectar) and an independent, weaker effect of higher aphid abundance on females (density‐mediated indirect effect). Conversely, the female bias for predators was driven solely by the greater attractiveness of female plants. We did not find interaction modification, i.e., ant–aphid and predator–aphid interactions were equivalent between plant sexes. Plant sex explained 0.24%, 2.28%, and 4.42% of the variance in aphids, predators, and ants, respectively, values comparable to but slightly weaker than those previously reported from common‐garden studies. In contrast to the prediction of diminished plant genetic effects with increasing trophic level, we show how weak indirect effects on predators and parasitoids (via herbivores) can be complemented by strong direct effects via common plant traits (floral resources). In summary, we document direct and indirect effects of genetically based sex on a multi‐trophic arthropod community that were expressed in wild‐grown plants across multiple years.

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Sensitivity of survival to migration routes used by juvenile Chinook salmon to negotiate the Sacramento-San Joaquin River Delta - Russell W. Perry; Patricia L. Brandes; Jon R. Burau; A. Peter Klimley; Bruce MacFarlane; Cyril Michel; John R. Skalski (Environmental Biology of Fishes, 2013)

Effects of Spatially Extensive Control of Invasive Rats on Abundance of Native Invertebrates in Mainland New Zealand Forests - WENDY A. RUSCOE; PETER J. SWEETAPPLE; MIKE PERRY; RICHARD P. DUNCAN (Conservation Biology, 2013)
Predation on native fauna by non‐native invasive mammals is widely documented, but effects of predation at the population level are rarely measured. Eradication of invasive mammals from islands has led to recovery of native biota, but the benefits of controlling invasive mammal populations in settings where eradication is not feasible are less understood. We used various combinations of aerially delivered toxic bait and control measures on the ground to reduce abundances of invasive rats (Rattus rattus) to low levels over large areas on mainland New Zealand and then monitored the abundance of invertebrates on replicated treatment sites to compare with abundances on similar nontreatment sites. We also assessed rat diet by examining stomach contents. Abundance of the rats’ most‐consumed invertebrate prey item, the large‐bodied Auckland tree weta (Hemideina thoracica), increased 3‐fold on treatment sites where we maintained rats at . Efectos del Control Extensivo Espacial de Ratas Invasoras sobre la Abundancia de Invertebrados Nativos en Bosques de Nueva Zelanda

Vegetation dynamics across a chronosequence of created wetland sites in Virginia, USA - Douglas A. DeBerry; James E. Perry (Wetlands Ecology and Management, 2012)

Oxidative Damage to RNA in Aging and Neurodegenerative Disorders - Akihiko Nunomura; Paula I. Moreira; Rudy J. Castellani; Hyoung-gon Lee; Xiongwei Zhu; Mark A. Smith; George Perry (Neurotoxicity Research, 2012)

Follicular determinants of pregnancy establishment and maintenance - Ky G. Pohler; Thomas W. Geary; Jacqueline A. Atkins; George A. Perry; Emma M. Jinks; Michael F. Smith (Cell and Tissue Research, 2012)

Nitrogen fixation by pea and lentil green manures in a semi-arid agroecoregion: effect of planting and termination timing - Ann M. McCauley; Clain A. Jones; Perry R. Miller; Macdonald H. Burgess; Catherine A. Zabinski (Nutrient Cycling in Agroecosystems, 2012)

Ω3-Polyunsaturated fatty acids prevent lipoperoxidation, modulate antioxidant enzymes, and reduce lipid content but do not alter glycogen metabolism in the livers of diabetic rats fed on a high fat thermolyzed diet - Adriano M. de Assis; Anderson Rech; Aline Longoni; Liane N. Rotta; Cristiane C. Denardin; Matheus A. Pasquali; Diogo O. Souza; Marcos L. S. Perry; José C. Moreira (Molecular and Cellular Biochemistry, 2012)

Compensatory regulation of acid–base balance during salinity transfer in rainbow trout (Oncorhynchus mykiss) - K. M. Gilmour; S. F. Perry; A. J. Esbaugh; J. Genz; J. R. Taylor; M. Grosell (Journal of Comparative Physiology B, 2012)

Sildenafil does not improve steady state cardiovascular hemodynamics, peak power, or 15-km time trial cycling performance at simulated moderate or high altitudes in men and women - Jochen Kressler; Mark Stoutenberg; Bernard A. Roos; Anne L. Friedlander; Arlette C. Perry; Joseph F. Signorile; Kevin A. Jacobs (European Journal of Applied Physiology, 2011)

Drivers of region-wide declines in architectural complexity on Caribbean reefs - Lorenzo Alvarez-Filip; J. A. Gill; N. K. Dulvy; A. L. Perry; A. R. Watkinson; I. M. Côté (Coral Reefs, 2011)

Optimal plant densities of lucerne (Medicago sativa) for pasture production and soil water extraction in mixed pastures in south-western Australia - Perry J. Dolling; Anita M. Lyons; Roy A. Latta (Plant and Soil, 2011)

FUS Immunogold Labeling TEM Analysis of the Neuronal Cytoplasmic Inclusions of Neuronal Intermediate Filament Inclusion Disease: A Frontotemporal Lobar Degeneration with FUS Proteinopathy - Tristan Page; Michael A. Gitcho; Sabrina Mosaheb; Deborah Carter; Sumi Chakraverty; Robert H. Perry; Eileen H. Bigio; Marla Gearing; Isidre Ferrer; Alison M. Goate; Nigel J. Cairns; Julian R. Thorpe (Journal of Molecular Neuroscience, 2011)

Effect of methamphetamine dependence on inhibitory deficits in a novel human open-field paradigm - Brook L. Henry; Arpi Minassian; Mandy van Rhenen; Jared W. Young; Mark A. Geyer; William Perry (Psychopharmacology, 2011)

The controls on phosphorus availability in a Boreal lake ecosystem since deglaciation - Stephen A. Norton; Randall H. Perry; Jasmine E. Saros; George L. Jacobson; Ivan J. Fernandez; Jiří Kopáček; Tiffany A. Wilson; Michael D. SanClements (Journal of Paleolimnology, 2011)

Status and future of the forest health indicators program of the USA - Christopher William Woodall; Michael C. Amacher; William A. Bechtold; John W. Coulston; Sarah Jovan; Charles H. Perry; KaDonna C. Randolph; Beth K. Schulz; Gretchen C. Smith; Borys Tkacz; Susan Will-Wolf (Environmental Monitoring and Assessment, 2011)

Green manure and phosphate rock effects on phosphorus availability in a northern Great Plains dryland organic cropping system - Terry L. Rick; Clain A. Jones; Richard E. Engel; Perry R. Miller (Organic Agriculture, 2011)

A “Driving Force” in Developing the Nation's Forests: The McIntire-Stennis Cooperative Forestry Research Program - Steven H. Bullard; Perry J. Brown; Catalino A. Blanche; Richard W. Brinker; Don H. Thompson (Journal of Forestry, 2011)
The McIntire-Stennis (M-S) Cooperative Forestry Research Program has provided fundamental support for creating and strengthening forestry research and graduate training efforts at colleges and universities across the nation for nearly 50 years. M-S funding has helped produce thousands of forestry scientists and other research professionals, and M-S—supported research has provided critical basic understanding and applied solutions to extend the benefits that flow from forests and related rangelands across the nation over time. The 1962 legislation that created the M-S program authorized funding of up to one-half of the funds appropriated for federal forestry research conducted directly by the USDA. Throughout the program's history, however, M-S appropriations have been far below the authorized level. In 2012, the M-S program's 50th anniversary will be celebrated. Congress and the President therefore have a truly significant “golden anniversary” opportunity to strengthen the nation's investment in research and training that represents an essential and powerful “driving force behind progress” in sustaining forests for ecological, economic, and social benefits for present and future generations.

Width of riparian buffer and structure of adjacent plantations influence occupancy of conservation priority birds - Roger W. Perry; T. Bently Wigley; M. Anthony Melchiors; Ronald E. Thill; Philip A. Tappe; Darren A. Miller (Biodiversity and Conservation, 2011)

Characterization of a legumain/vacuolar processing enzyme and YVADase activity in Papaver pollen - Maurice Bosch; Natalie S. Poulter; Ruth M. Perry; Katie A. Wilkins; Vernonica E. Franklin-Tong (Plant Molecular Biology, 2010)

Regional differences in awareness and attitudes regarding genetic testing for disease risk and ancestry - Charles R. Jonassaint; Eunice R. Santos; Crystal M. Glover; Perry W. Payne; Grace-Ann Fasaye; Nefertiti Oji-Njideka; Stanley Hooker; Wenndy Hernandez; Morris W. Foster; Rick A. Kittles; Charmaine D. Royal (Human Genetics, 2010)

Winter as a nutritional bottleneck for North American porcupines (Erethizon dorsatum) - Jessica A. Coltrane; Perry S. Barboza (Journal of Comparative Physiology B, 2010)

Breaking the language barrier: experimental evolution of non-native Vibrio fischeri in squid tailors luminescence to the host - Brian M. Schuster; Lauren A. Perry; Vaughn S. Cooper; Cheryl A. Whistler (Symbiosis, 2010)

Polyamines are required for the expression of key Hms proteins important for Yersinia pestis biofilm formation - Brian W. Wortham; Marcos A. Oliveira; Jacqueline D. Fetherston; Robert D. Perry (Environmental Microbiology, 2010)
Summary We previously showed that mutations in the genes encoding the two main biosynthetic enzymes responsible for polyamine production, arginine decarboxylase (SpeA) and ornithine decarboxylase (SpeC) cause a loss of biofilm formation in Yersinia pestis . In Y. pestis the development of a biofilm is dependent on 6 Hms (hemin storage) proteins (HmsH, F, R, S, T and P) grouped into 3 operons; hmsHFRS , hmsT and hmsP . In this article we show that polyamines are necessary to maintain the levels of key Hms proteins. In the absence of polyamines there is an ∼93%, ∼43% and ∼90% reduction in protein levels of HmsR, HmsS and HmsT respectively. Overexpression of hmsR and hmsT from plasmids alone can restore biofilm formation to a SpeA ‐ SpeC ‐ mutant. Addition of exogenous putrescine also restores normal levels of HmsR, HmsS, HmsT and biofilm production. Analyses using transcriptional reporters and quantitative RT‐PCR indicate that the initiation of transcription and mRNA stability are not reduced by polyamine deficiency. Instead, translational reporters indicate that polyamines function at least in part by modulating the translation of HmsR and HmsT. Although construction of a consensus Shine–Dalgarno sequence upstream of hmsT modestly reduced the stimulation of translation by putrescine, additional mechanisms likely contribute to the polyamine‐dependent expression of HmsT. Finally, we have shown that polyamines play a role in bubonic plague.

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Nicotine self-administration in the rat: effects of hypocretin antagonists and changes in hypocretin mRNA - Mark G. LeSage; Jennifer L. Perry; Catherine M. Kotz; David Shelley; William A. Corrigall (Psychopharmacology, 2010)

Microbial degradation of usnic acid in the reindeer rumen - Monica A. Sundset; Perry S. Barboza; Thomas K. Green; Lars P. Folkow; Arnoldus Schytte Blix; Svein D. Mathiesen (The Science of Nature, 2010)

GBR 12909 administration as a mouse model of bipolar disorder mania: mimicking quantitative assessment of manic behavior - Jared W. Young; Andrew K. L. Goey; Arpi Minassian; William Perry; Martin P. Paulus; Mark A. Geyer (Psychopharmacology, 2010)

Physical integrity: the missing link in biological monitoring and TMDLs - Brenda Asmus; Joseph A. Magner; Bruce Vondracek; Jim Perry (Environmental Monitoring and Assessment, 2009)

Deer Responses to Repellent Stimuli - Bruce A. Kimball; Jimmy Taylor; Kelly R. Perry; Christina Capelli (Journal of Chemical Ecology, 2009)

Native cover crops suppress exotic annuals and favor native perennials in a greenhouse competition experiment - Laura G. Perry; Spencer A. Cronin; Mark W. Paschke (Plant Ecology, 2009)

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Tree canopy effect on grass and grass/legume mixtures in eastern Nebraska - Michael E. L. Perry; Walter H. Schacht; Gregory A. Ruark; James R. Brandle (Agroforestry Systems, 2009)

The effects of bottom-up target luminance and top-down spatial target predictability on saccadic reaction times - Robert A. Marino; Douglas Perry Munoz (Experimental Brain Research, 2009)

The fire frequency analysis branch of the pyrostatistics tree: sampling decisions and censoring in fire interval data - Max A. Moritz; Tadashi J. Moody; Lori J. Miles; Matthew M. Smith; Perry de Valpine (Environmental and Ecological Statistics, 2009)

QTL, additive and epistatic effects for SCN resistance in PI 437654 - Xiaolei Wu; Sean Blake; David A. Sleper; J. Grover Shannon; Perry Cregan; Henry T. Nguyen (Theoretical and Applied Genetics, 2009)

Ecosystem effects of expanding populations of Avicennia germinans in a Louisiana salt marsh - Carey Lynn Perry; Irving A. Mendelssohn (Wetlands, 2009)

Effects of nicotine on sensorimotor gating impairment induced by long-term treatment with neurotoxic NMDA antagonism - Bruce A. Rasmussen; David C. Perry; Jahn O’Neil; Kebreten F. Manaye; Yousef Tizabi (Neurotoxicity Research, 2008)

The NIF LinkOut Broker: A Web Resource to Facilitate Federated Data Integration using NCBI Identifiers - Luis Marenco; Giorgio A. Ascoli; Maryann E. Martone; Gordon M. Shepherd; Perry L. Miller (Neuroinformatics, 2008)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

Introduction to the Limnology and Oceanography Special Issue on Autonomous and Lagrangian Platforms and Sensors (ALPS) - T. D. Dickey; E. C. Itsweire; M. A. Moline; M. J. Perry (Limnology and Oceanography, 2008)
This issue is devoted to recent developments of autonomous and Lagrangian platforms and sensors (ALPS) and their uses for solving a broad range of interdisciplinary aquatic problems. The collective papers treat a variety of problems that generally require measurements spanning a continuum of temporal and spatial scales. ALPS platforms in this issue include surface drifters, profiling and other types of subsurface floats, gliders, unmanned boats, autonomous underwater vehicles, and instrumented animals. ALPS platforms can provide access in difficult environments (e.g., under ice and in high‐sea states). They are also important for emerging networked ocean and lake observing systems that require continuous measurements and near‐real‐time data. This introductory paper provides historical perspectives, background, motivation for the issue, and a tabular summary of papers in the present collection.

Manipulating Beaver (Castor canadensis) Feeding Responses to Invasive Tamarisk (Tamarix spp.) - Bruce A. Kimball; Kelly R. Perry (Journal of Chemical Ecology, 2008)

An extract of Salvia (sage) with anticholinesterase properties improves memory and attention in healthy older volunteers - Andrew B. Scholey; Nicola T. J. Tildesley; Clive G. Ballard; Keith A. Wesnes; Andrea Tasker; Elaine K. Perry; David O. Kennedy (Psychopharmacology, 2008)

Shallow plumbing systems for small-volume basaltic volcanoes - Gordon N. Keating; Greg A. Valentine; Donathon J. Krier; Frank V. Perry (Bulletin of Volcanology, 2008)

The role of novel chitin-like polysaccharides in Alzheimer disease - Rudy J. Castellani; George Perry; Mark A. Smith (Neurotoxicity Research, 2007)

First EFSA experiences with monitoring plans - Detlef Bartsch; A. Gathmann; S. Hartley; N. B. Hendriksen; R. Hails; K. Lheureux; J. Kiss; S. Mesdagh; G. Neemann; J. Perry; S. Renckens; J. Schiemann; et al. (Journal of Consumer Protection and Food Safety, 2007)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Regression Techniques for Examining Land Use/Cover Change: A Case Study of a Mediterranean Landscape - James D. A. Millington; George L. W. Perry; Raúl Romero-Calcerrada (Ecosystems, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

Long-term effects of developmental PCP administration on sensorimotor gating in male and female rats - Bruce A. Rasmussen; Jahn O’Neil; Kebreten F. Manaye; David C. Perry; Yousef Tizabi (Psychopharmacology, 2007)

Groundwater abstraction impacts on spring flow and base flow in the Hillsborough River Basin, Florida, USA - Kenneth A. Weber; Robert G. Perry (Hydrogeology Journal, 2006)

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Debate: “Is Increasing Neuroinflammation Beneficial for Neural Repair?” - Keith A. Crutcher; Howard E. Gendelman; Jonathan Kipnis; J. Regino Perez-Polo; V. H. Perry; Phillip G. Popovich; Lynne C. Weaver (Journal of Neuroimmune Pharmacology, 2006)

Prefrontal GABA levels in cocaine-dependent subjects increase with pramipexole and venlafaxine treatment - Chris C. Streeter; John Hennen; Yong Ke; J. Eric Jensen; Ofra Sarid-Segal; Leanne E. Nassar; Clifford Knapp; Angela A. Meyer; Tae Kwak; Perry F. Renshaw; Domenic A. Ciraulo (Psychopharmacology, 2006)

Overexpression of GRK2 in alzheimer disease and in a chronic hypoperfusion rat model is an early marker of brain mitochondrial lesions - Mark E. Obrenovich; Mark A. Smith; Sandra L. Siedlak; Shu G. Chen; Jack C. De La Torre; George Perry; Gjumrakch Aliev (Neurotoxicity Research, 2006)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Prefrontal and temporal gray matter density decreases in opiate dependence - In Kyoon Lyoo; Mark H. Pollack; Marisa M. Silveri; Kyung Heup Ahn; Claudia I. Diaz; Jaeuk Hwang; Seog Ju Kim; Deborah A. Yurgelun-Todd; Marc J. Kaufman; Perry F. Renshaw (Psychopharmacology, 2006)

Midwestern streamflow, precipitation, and atmospheric vorticity influenced by pacific sea-surface temperatures and total solar-irradiance variations - Charles A. Perry (International Journal of Climatology, 2006)

Anaerobic redox cycling of iron by freshwater sediment microorganisms - Karrie A. Weber; Matilde M. Urrutia; Perry F. Churchill; Ravi K. Kukkadapu; Eric E. Roden (Environmental Microbiology, 2006)
Summary The potential for microbially mediated anaerobic redox cycling of iron (Fe) was examined in a first‐generation enrichment culture of freshwater wetland sediment microorganisms. Most probable number enumerations revealed the presence of significant populations of Fe(III)‐reducing (approximately 10 8 cells ml −1 ) and Fe(II)‐oxidizing, nitrate‐reducing organisms (approximately 10 5 cells ml −1 ) in the freshwater sediment used to inoculate the enrichment cultures. Nitrate reduction commenced immediately following inoculation of acetate‐containing (approximately 1 mM) medium with a small quantity (1% v/v) of wetland sediment, and resulted in the transient accumulation of NO 2 − and production of a mixture of gaseous end‐products (N 2 O and N 2 ) and NH 4 + . Fe(III) oxide (high surface area goethite) reduction took place after NO 3 − was depleted and continued until all the acetate was utilized. Addition of NO 3 − after Fe(III) reduction ceased resulted in the immediate oxidation of Fe(II) coupled to reduction of NO 3 − to NH 4 + . No significant NO 2 − accumulation was observed during nitrate‐dependent Fe(II) oxidation. No Fe(II) oxidation occurred in pasteurized controls. Microbial community structure in the enrichment was monitored by denaturing gradient gel electrophoresis analysis of polymerase chain reaction‐amplified 16S rDNA and reverse transcription polymerase chain reaction‐amplified 16S rRNA, as well as by construction of 16S rDNA clone libraries for four different time points during the experiment. Strong similarities in dominant members of the microbial community were observed in the Fe(III) reduction and nitrate‐dependent Fe(II) oxidation phases of the experiment, specifically the common presence of organisms closely related (≥ 95% sequence similarity) to the genera Geobacter and Dechloromonas . These results indicate that the wetland sediments contained organisms such as Geobacter sp. which are capable of both dissimilatory Fe(III) reduction and oxidation of Fe(II) with reduction of NO 3 − to NH 4 + . Our findings suggest that microbially catalysed nitrate‐dependent Fe(II) oxidation has the potential to contribute to a dynamic anaerobic Fe redox cycle in freshwater sediments.

Prefrontal GABA levels in cocaine-dependent subjects increase with pramipexole and venlafaxine treatment - Chris C. Streeter; John Hennen; Yong Ke; J. Eric Jensen; Ofra Sarid-Segal; Leanne E. Nassar; Clifford Knapp; Angela A. Meyer; Tae Kwak; Perry F. Renshaw; Domenic A. Ciraulo (Psychopharmacology, 2005)

Neurotoxic dopamine quinone facilitates the assembly of tau into fibrillar polymers - Ismael Santa-María; Félix Hernández; Mark A. Smith; George Perry; Jesús Avila; Francisco J. Moreno (Molecular and Cellular Biochemistry, 2005)

Fishing for Answers with Transposons - Shannon A. Wadman; Karl J. Clark; Perry B. Hackett (Marine Biotechnology, 2005)

Adjunctive therapies for HIV-1 associated neurologic disease - Seth W. Perry; John P. Norman; Harris A. Gelbard (Neurotoxicity Research, 2005)

Deconstruction of Historic Mercury Accumulation in Lake Sediments, Northeastern United States - Ethan Perry; Stephen A. Norton; Neil C. Kamman; P. M. Lorey; Charles T. Driscoll (Ecotoxicology, 2005)

Retinoic acid isomers protect hippocampal neurons from amyloid-β induced neurodegeneration - Mehmet Sahin; Sibel Berker Karaüzüm; George Perry; Mark A. Smith; Yakup Alicigüzel (Neurotoxicity Research, 2005)

Functional MRI study of working memory in MDMA users - F. Gerard Moeller; Joel L. Steinberg; Donald M. Dougherty; Ponnada A. Narayana; Larry A. Kramer; Perry F. Renshaw (Psychopharmacology, 2004)

Predicting Cotton Lint Yield Maps from Aerial Photographs - G. Vellidis; M. A. Tucker; C. D. Perry; D. L. Thomas; N. Wells; C. K. Kvien (Precision Agriculture, 2004)

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Forest Structure and Fire Susceptibility in Volcanic Landscapes of the Eastern High Cascades, Oregon - DAVID A. PERRY; HUANG JING; ANDREW YOUNGBLOOD; DOUG R. OETTER (Conservation Biology, 2004)
Multidimensional forest health initiatives—those designed to restore and protect forest integrity in the large sense—require, among other things, a better understanding of the relationship between the structure of forests and (1) their susceptibility to wildfires outside the range of natural variability and (2) the level of treatment (if any) required to lower susceptibility into an acceptable range. Within the ponderosa pine zone (Pinus ponderosa Dougl. ex Laws.) on the eastern slopes of Oregon's Cascade Range, an average of 86% of trees >5 cm in diameter at breast height (dbh) were less than 101 years old, the density of young trees correlating negatively with the density of old trees (>150 yrs). Species composition differed significantly between age classes: 72% of trees older than 150 years were ponderosa pine, whereas 83% of trees younger than 101 years were either grand fir ( Abies grandis [Dougl.] Lindl.) or lodgepole pine ( Pinus contorta Dougl. ex). Loud Crown bulk density calculated to reflect the multiple canopy layer structure of these stands (CBDm) averaged 0.049 kg/m 3 , compared to 0.093 kg/m 3 using the standard approach ( p 2 = 0.92), implying that over certain ranges small changes in basal area result in relatively large changes in susceptibility (assuming that changes in basal area are due to addition or removal of smaller trees). Landsat thematic mapper correlates reasonably well with CBDm ( r 2 = 0.80) and may provide a tool for rapid risk assessment.

Nuclear organization of centromeric domains is not perturbed by inhibition of histone deacetylases - Susan Gilchrist; Nick Gilbert; Paul Perry; Wendy A. Bickmore (Chromosome Research, 2004)

The Genetic Basis of Resistance to Diazinon in Natural Populations of Drosophila melanogaster - Fiona M. Pyke; Michael R. Bogwitz; Trent Perry; Adrian Monk; Philip Batterham; John A. McKenzie (Genetica, 2004)

Low doses of domoic acid during postnatal development produce permanent changes in rat behaviour and hippocampal morphology - T. A. Doucette; P. B. Bernard; H. Husum; M. A. Perry; C. L. Ryan; R. A. Tasker (Neurotoxicity Research, 2004)

Methods of screening apricot fruit for resistance to brown rot caused by Monilinia spp. - Monika Walter; Gillian F. McLaren; Jenny A. Fraser; Chris M. Frampton; Kirsty S. H. Boyd-Wilson; Joanne H. Perry (Australasian Plant Pathology, 2004)

Biological degradation of coral framework in a turbid lagoon environment, Discovery Bay, north Jamaica - I. A. Macdonald; C. T. Perry (Coral Reefs, 2003)

Interspecific Interactions Between Cebus capucinus and Other Species: Data from Three Costa Rican Sites - Lisa M. Rose; Susan Perry; Melissa A. Panger; Katharine Jack; Joseph H. Manson; Julie Gros-Louis; Katherine C. Mackinnon; Erin Vogel (International Journal of Primatology, 2003)

A new mode of parental care in cockroaches - J. Perry; C. A. Nalepa (Insectes Sociaux, 2003)

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

Variation in propensity to defend by reproductive gall morphs in two species of gall-forming thrips - S. P. Perry; M. J. McLeish; M. P. Schwarz; A. H. Boyette; J. Zammit; T. W. Chapman (Insectes Sociaux, 2003)

Role of vascular hypoperfusion-induced oxidative stress and mitochondria failure in the pathogenesis of Alzheimer disease - Gjumrakch Aliev; Mark A. Smith; Mark E. Obrenovich; Jack C. de la Torre; George Perry (Neurotoxicity Research, 2003)

Stable isotope systematics of two cenotes from the northern Yucatan Peninsula, Mexico - Richard A. Socki; Eugene Jr. C. Perry; Christopher S. Romanek (Limnology and Oceanography, 2002)
Deep water‐filled sinkholes, cenotes, are common in the northern Yucatan Peninsula. At least five of these cenotes are deep enough to extend through a freshwater lens of meteoric origin in which δ 18 O and δD follow the trend δD = 8.11 × δ 18 O + 10.4. Below this freshwater lies saline water that originated as seawater and has retained its seawater isotopic identity. Deep cenotes, characterized by input of variable amounts of organic debris from tropical vegetation and by poor circulation below the fresh‐/saltwater interface, provide excellent water columns in which to study sulfur redox phenomena. Measurements include O, H, and S isotope composition, conductivity, sulfur speciation, and pH from two cenotes (Ucil, 98 m deep, and Xcolac, 125 m deep). Strong 34S enrichment of sulfate and 34 S depletion of sulfide indicate anaerobic bacterial reduction of sulfate. A shift in the isotopic composition of sulfur in Xcolac from a seawater value of +21.0‰ (CDT) to +41.8‰ indicates conversion of sulfate to isotopically light sulfide. Mass balance calculations indicate that escape of isotopically light sulfur from the system is a slow process. At 80 m in Xcolac, a difference in sulfur isotope composition between sulfate and sulfide (△34S) of 63.2‰ is observed and could be the result of multiple sulfate reduction reactions. Higher in the water column, sulfide oxidation occurs, probably the result of bacterially mediated sulfide oxidation processes. A deep observation well (lacking organic matter input) shows only a slight deviation in sulfur isotope composition of sulfate from seawater values.

Planktonic copepods from temporary marshes in Everglades National Park (Florida, U.S.A.) - M. C. Bruno; G. Sagnotti; S. A. Perry (Hydrobiologia, 2002)

Use of telemetry in the development and application of biological criteria for habitat hydraulic modeling - D. A. Scruton; K. D. Clarke; L. M. N. Ollerhead; D. Perry; R. S. McKinley; K. Alfredsen; A. Harby (Hydrobiologia, 2002)

In Search of Effective Scales for Stream Management: Does Agroecoregion, Watershed, or Their Intersection Best Explain the Variance in Stream Macroinvertebrate Communities? - A. L. DOVCIAK; J. A. PERRY (Environmental Management, 2002)

Spatially explicit population responses of crayfish Procambarus alleni to potential shifts in vegetation distribution in the marl marshes of Everglades National Park, USA - Charles A. Acosta; Sue A. Perry (Hydrobiologia, 2002)

Fluoxetine, but not other selective serotonin uptake inhibitors, increases norepinephrine and dopamine extracellular levels in prefrontal cortex - Frank P. Bymaster; Wei Zhang; Petra A. Carter; Janice Shaw; Eyassu Chernet; Lee Phebus; David T. Wong; Kenneth W. Perry (Psychopharmacology, 2002)

Involvement of maillard reactions in Alzheimer disease - V. Prakash Reddy; Mark E. Obrenovich; Craig S. Atwood; George Perry; Mark A. Smith (Neurotoxicity Research, 2002)

Tumor Necrosis Factor-Alpha in Normal and Diseased Brain: Conflicting Effects Via Intraneuronal Receptor Crosstalk? - Seth W Perry; Stephen Dewhurst; Matthew J Bellizzi; Harris A Gelbard (Journal of NeuroVirology, 2002)

Differentiation of Gut and Hepatic First-Pass Effect of Drugs: 1. Studies of Verapamil in Ported Dogs - Yong-Hee Lee; Barbara A. Perry; Hee-Sang Lee; Jeevan R. Kunta; John P. Sutyak; Patrick J. Sinko (Pharmaceutical Research, 2001)

Diapause in copepods (Crustacea) from ephemeral habitats with different hydroperiods in Everglades National Park (Florida, U.S.A.) - Maria Cristina Bruno; William F. Loftus; Janet W. Reid; Sue A. Perry (Hydrobiologia, 2001)

Differential growth of crayfish Procambarus alleni in relation to hydrological conditions in marl prairie wetlands of Everglades National Park, USA - Charles A. Acosta; Sue A. Perry (Aquatic Ecology, 2000)

Mechanomyographic and electromyographic responses during submaximal cycle ergometry - Terry J. Housh; Sharon R. Perry; Anthony J. Bull; Glen O. Johnson; Kyle T. Ebersole; Dona J. Housh; Herbert A. deVries (European Journal of Applied Physiology, 2000)

Drift and benthic invertebrate responses to stepwise and abrupt increases in non-scouring flow - J. Bosco Imbert; James A. Perry (Hydrobiologia, 2000)

Paleogenetic evidence for a past invasion of Onondaga Lake, New York, by exotic Daphnia curvirostris using mtDNA from dormant eggs - Meghan A. Duffy; Linda J. Perry; Colleen M. Kearns; Lawrence J. Weider; Nelson G. Hairston (Limnology and Oceanography, 2000)
Cladocerans possess traits such as resistant diapausing eggs and rapid parthenogenetic reproduction that make them efficient invaders of new habitats. Nearly all known invasions have been successful, perhaps because failed invasions are difficult to detect. It is possible, however, to identify past failed invasions, by studying the diapausing egg bank. Daphnia ephippia were found in the sediments of Onondaga Lake, New York that could neither be hatched nor identified using egg‐case morphology. Instead, we used sequences of the 12S ribosomal ribonucleic acid (rRNA) gene of mitochondrial deoxyribonucleic acid (mtDNA) extracted from diapausing eggs to identify the unknown Daphnia . We compared these DNA sequences with those generated from morphologically identified Daphnia species collected in Onondaga Lake, and with published sequences for other North American Daphnia species. The invader was identified as Daphnia curvirostris , a Eurasian species that has been only reported once before from North America, in extreme northwestern Canada. The discovery of it in Onondaga Lake signifies a greater than 4,500‐km range extension for this species. On the basis of the sediment ephippial data, D. curvirostris first appeared in the lake about 1952, reached maximum abundance during the period of peak pollution (1950s–1980s), and then essentially disappeared after 1983 when lake water quality improved. As with the finding of another exotic cladoceran, D. exilis , in Onondaga Lake (Hairston et al. 1999 a ), it is likely that chemical industry activities on the lakeshores were the original source of invading D. curvirostris , that pollution allowed this species to become established in the lake, and that the reduction in pollution ultimately led to its disappearance from the water column.

DNA sequence analysis identifies genetically distinguishable populations of harp seals ( Pagophilus groenlandicus ) in the Northwest and Northeast Atlantic - E. A. Perry; G. B. Stenson; S. E. Bartlett; W. S. Davidson; S. M. Carr (Marine Biology, 2000)

Regional Differences in Intestinal Spreading and pH Recovery and the Impact on Salmon Calcitonin Absorption in Dogs - Yong-Hee Lee; Barbara A. Perry; John P. Sutyak; William Stern; Patrick J. Sinko (Pharmaceutical Research, 2000)

Environmental influences on the availability of smooth pink shrimp, Pandalus jordani , to commercial fishing gear off Vancouver Island, Canada - R. Ian Perry; James A. Boutillier; Michael G.G. Foreman (Fisheries Oceanography, 2000)
Short time scale (less than seasonal) variability in commercial catch rates of smooth pink shrimp, Pandalus jordani, off the west coast of Vancouver Island, Canada, was examined in relation to changes in environmental conditions. Catch per unit of effort (CPUE) data were used as a proxy for catchability to identify environmental conditions affecting the availability of shrimp to the two main gear types in this fishery: otter trawls and beam trawls. Correlogram analyses of the 1996 CPUE (log‐transformed) data from each gear type, and autocorrelation analyses of wind stress, tidal current speed, sea surface temperature and salinity, and hours of bright sunshine (the latter three as residuals from their seasonal trends) for 1996 indicated a mean decorrelation time scale of 7.7 days. This was used to construct smoothed time series of these CPUE and environmental data for 1996. Multiple regression analyses with CPUE as the dependent variable and the environmental data as independent variables were significant, explaining 44% of the variability in otter‐trawl data and 35% of the beam‐trawl variability. Three hypotheses are proposed to explain these results, involving interactions between the shrimp’s behaviour and environmental conditions. A significant proportion of the within‐season variability in CPUE (and therefore in the availability of shrimp to fishing gear) for P. jordani off Vancouver Island can result from variations in environmental conditions which, if included in stock analyses, should reduce the variability of population abundance estimates.

Sex differences in sensorimotor gating of the human startle reflex: all smoke? - N. R. Swerdlow; M. A. Geyer; P. L. Hartman; J. Sprock; P. P. Auerbach; K. Cadenhead; W. Perry; D. L. Braff (Psychopharmacology, 1999)

Impact of Regional Intestinal pH Modulation on Absorption of Peptide Drugs: Oral Absorption Studies of Salmon Calcitonin in Beagle Dogs - Yong-Hee Lee; Barbara A. Perry; Stacy Labruno; Hee Sang Lee; William Stern; Lisa M. Falzone; Patrick J. Sinko (Pharmaceutical Research, 1999)

The influence of chronic anaemia on catecholamine secretion in the rainbow trout ( Oncorhynchus mykiss ) - S. F. Perry; C. J. Montpetit; A. E. Julio; K. Moore (Journal of Comparative Physiology B, 1999)

A framework for providing scientific advice for the management of new and developing invertebrate fisheries - R. Ian Perry; Carl J. Walters; James A. Boutillier (Reviews in Fish Biology and Fisheries, 1999)

Transferring soils from high‐ to low‐elevation forests increases nitrogen cycling rates: climate change implications - Stephen C. Hart; David A. Perry (Global Change Biology, 1999)
We assessed the potential impact of global warming resulting from a doubling of preindustrial atmospheric CO 2 on soil net N transformations by transferring intact soil cores (0–15 cm) from a high‐elevation old‐growth forest to a forest about 800 m lower in elevation in the central Oregon Cascade Mountains, USA. The lower elevation site had mean annual air and soil (10‐cm mineral soil depth) temperatures about 2.4 and 3.9 °C higher than the high‐elevation site, respectively. Annual rates of soil net N mineralization and nitrification more than doubled in soil transferred to the low‐elevation site (17.2–36.0 kg N ha –1 and 5.0–10.7 kg NO 3 – –N ha –1 , respectively). Leaching of inorganic N from the surface soil (in the absence of plant uptake) also increased. The reciprocal treatment (transferring soil cores from the low‐ to the high‐elevation site) resulted in decreases of about 70, 80, and 65% in annual rates of net N mineralization, nitrification, and inorganic N leaching, respectively. Laboratory incubations of soils under conditions of similar temperature and soil water potential suggest that the quality of soil organic matter is higher at the high‐elevation site. Similar in situ rates of soil net N transformations between the two sites occurred because the lower temperature counteracts the effects of greater substrate quantity and quality at the high elevation site. Our results support the hypothesis that high‐elevation, old‐growth forest soils in the central Cascades have higher C and N storage than their low‐elevation analogues primarily because low temperatures limit net C and N mineralization rates at higher elevations.

Habitat partitioning in a community of darters in the Elk River, West Virginia - Stuart A. Welsh; Sue A. Perry (Environmental Biology of Fishes, 1998)

Analyzing maps of dispersal around a single focus - S. Korie; S.J Clark; J.N Perry; M. A. Mugglestone; P .W. Bartlett; E. J . P. Marshall; J. A. Mann (Environmental and Ecological Statistics, 1998)

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific - C. S. BAKER; L. MEDRANO‐GONZALEZ; J. CALAMBOKIDIS; A. PERRY; F. PICHLER; H. ROSENBAUM; J. M. STRALEY; J. URBAN‐RAMIREZ; M. YAMAGUCHI; O. VON ZIEGESAR (Molecular Ecology, 1998)
The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of target sequences amplified by the polymerase chain reaction (PCR–RFLP). There was little evidence of heterogeneity in the frequencies of mtDNA haplotypes or actin intron alleles due to the year or sex composition of the sample. However, frequencies of four mtDNA haplotypes showed marked regional differences in their distributions (Φ ST = 0.277; P n = 205 individuals) while the two alleles showed significant, but less marked, regional differences (Φ ST = 0.033; P n = 400 chromosomes). An hierarchical analysis of variance in frequencies of haplotypes and alleles supported the grouping of six regions into a central and eastern stock with further partitioning of variance among regions within stocks for haplotypes but not for alleles. Based on available genetic and demographic evidence, the southeastern Alaska and central California feeding grounds were selected for additional analyses of nuclear differentiation using allelic variation at four microsatellite loci. All four loci showed significant differences in allele frequencies (overall F ST = 0.043; P n = 139 chromosomes per locus), indicating at least partial reproductive isolation between the two regions as well as the segregation of mtDNA lineages. Although the two feeding grounds were not panmictic for nuclear or mitochondrial loci, estimates of long‐term migration rates suggested that male‐mediated gene flow was several‐fold greater than female gene flow. These results include and extend the range and sample size of previously published work, providing additional evidence for the significance of genetic management units within oceanic populations of humpback whales.

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

DNA fingerprinting evidence of nonfilial nursing in grey seals - ELIZABETH A. PERRY; DARYL J. BONESS; ROBERT C. FLEISCHER (Molecular Ecology, 1998)
We tested the hypothesis that kin selection may play a role in fostering behaviour in grey seals. Fostering frequency varied among three colonies, ranging from 3% to 28%. Band‐sharing coefficients (S) of DNA fingerprints, from two multilocus probes, were used to predict relatedness ( r ). Mean r did not differ between foster mother‐pup pairs and the expected r = 0 for presumed unrelated female‐pup pairs. Likewise, mean r between fostered and filial pups compared to r between presumed unrelated pups within the same beaches did not differ. Mean S values of presumed unrelated pups on different beaches within the two smallest colonies were indistinguishable, indicating that there is not increased variation in relatedness in small colonies. These results suggest that kin selection does not play a significant role in the maintenance of grey seal fostering behaviour.

GENETIC AND BEHAVIORAL EVIDENCE THAT HARBOR SEAL ( PHOCA VITULINA ) FEMALES MAY MATE WITH MULTIPLE MALES - E. A. Perry; W. Amos (Marine Mammal Science, 1998)

Increased metabolic cost of maintenance in hybrids of the stone crabs Menippe mercenaria and M. adina - C. A. Combs; R. P. Henry; T. M. Bert; H. M. Perry; M. West (Marine Biology, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Calcium binding and conformational properties of calmodulin complexed with peptides derived from myristoylated alanine-rich C kinase substrate (MARCKS) and MARCKS-related protein (MRP) - Tudor Porumb; A. Crivici; Perry J. Blackshear; M. Ikura (European Biophysics Journal, 1997)

Response of soil and leaf litter microarthropods to forest application of diflubenzuron - William B. Perry; Tim A. Christiansen; Sue A. Perry (Ecotoxicology, 1997)

Thermoleophilum album gen. nov. and sp. nov., a bacterium obligate for thermophily and n-alkane substrates - K. A. Zarilla; J. J. Perry (Archives of Microbiology, 1984)

Pesticide and PCB residues in the upper Snake River ecosystem, Southeastern Idaho, following the collapse of the Teton Dam 1976 - J. A. Perry (Archives of Environmental Contamination and Toxicology, 1979)

Experimental infection of the argasid tick, ornithodoros moubata porcinus, with African swine fever virus - W. Plowright; C. T. Perry; M. A. Peirce; J. Parker (Archives of Virology, 1970)

Redskin, a new red variety of potato resistant to scab, with high yielding ability, and adapted to growing conditions in the south - R. V. Akeley; Bruce A. Perry; Allen E. Schark (American Journal of Potato Research, 1961)

A potato breeding technique used for Texas - Bruce A. Perry; Robert V. Akeley; W. B. Cook (American Journal of Potato Research, 1960)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)